Solid composite material comprising nanoparticles and manganese, aluminum and optionally a carbon-based alloy, and method for producing same - Patents.com

By adding nanoparticles to magnetic materials and adopting specific alloy composition and heat treatment processes, the problems of τ phase instability and low purity are solved, and high magnetic and high coercivity performance is achieved, reducing the use of rare earth metals, reducing costs and environmental impacts.

JP7648533B2Active Publication Date: 2025-03-18HOGANAS AB
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021552546
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-05
Filing Date
2020-02-27
Publication Date
2025-03-18
Estimated Expiration
2040-02-27

AI Technical Summary

Technical Problem

During the processing process, existing magnetic materials are prone to instability and low purity of the t-phase, resulting in poor magnetic properties, and relying on rare earth metals, which have high costs and environmental pollution problems.

Method used

A solid composite material containing nanoparticles is used to improve the purity and stability of the tau phase through specific alloy compositions (such as MnAl alloys) and heat treatment processes to form high magnetic and high coercivity materials.

Benefits of technology

Magnetic materials with high magnetization and high coercivity are achieved, reducing the use of rare earth metals, reducing production costs and environmental impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648533000013
    Figure 0007648533000013
  • Figure 0007648533000014
    Figure 0007648533000014
  • Figure 0007648533000015
    Figure 0007648533000015
Patent Text Reader

Abstract

Provided are solid composite materials, and methods for producing them, comprising an alloy based on manganese, aluminum, and optionally carbon, and dispersed nanoparticles made from material X, which material X is different from manganese, aluminum, carbon, or a mixture thereof, and which meets the following requirements: The melting temperature of material X is 1400°C or higher, preferably 1500°C or higher; Material X satisfies the above requirement. The composite material is suitable as a magnetic material or precursor to a magnetic material, and the presence of the nanoparticles allows for improved magnetic properties compared to existing alloys based on manganese, aluminum, and optionally carbon. Magnetic materials in molded form comprising the composite material, and electric or electronic devices comprising the magnetic material, are also part of the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] In the most general terms, the present invention relates to improvements in the field of magnetic materials and magnets, as well as precursor materials for magnetic materials and magnets, and methods of producing or processing such materials. In particular, the present invention relates to solid composite materials comprising nanoparticles and alloy-based manganese, aluminum, and optionally carbon (e.g., manganese-aluminum (MnAl) alloys, optionally containing carbon, present predominantly in the τ or ε phase). The present invention aims to obtain such materials with improved properties, such as improved magnetic properties or improved crystallographic (X-ray) phase purity.

[0002] In one aspect, the invention relates to a solid composite material comprising nanoparticles made of material X and an optionally carbon-doped manganese-aluminium (MnAl) alloy with a high content of τ- or ε-phase, as well as a method for its manufacture. The solid composite material can be present in particulate form. The invention further relates to a shaped article obtained by processing the solid particulate composite material into a shaped body. The shaped body can be used as a magnet, for example in an electrical or electronic device. [Background technology]

[0003] Magnetic materials are used in many industrial electrical or electronic applications and devices, such as speaker systems, earphones, direct current electric motors in battery (primary or secondary) powered devices, and wind turbines, to name just a few.

[0004] However, such magnetic materials are expensive and, moreover, typically contain rare earth (RE) metals. The mining and refining of such rare earth metals is typically associated with high processing costs, environmental burdens, and health concerns. Thus, these conventional magnetic materials result in both high costs and high environmental burdens. Therefore, alternatives to these rare earth metal-based magnetic materials are desirable.

[0005] The low-cost, rare-earth-free tau phase of MnAl alloys has magnetic properties and is currently being studied in bonded NdFe 14 It is believed to have the potential to replace currently used magnets such as rare earth permanent magnets. 0 MnAl-based magnetic materials (about 50–60 atomic % Mn) with the type structure (τ-phase) have great potential to become low-cost, high-performance permanent magnet materials, especially if suitable processing routes can be developed.

[0006] Room-temperature stable phases in the MnAl phase diagram include γ2(Al8Mn5), β(Mn), and ferromagnetic τ-phase (see Figure 1). The most common approach to synthesize τ-phase MnAl alloys is by quenching the high-temperature ε-phase followed by heat treatment at 350-650 °C. However, the τ-phase is metastable, and it is difficult to obtain MnAl alloys containing the τ-phase in high purity. So far, various heat treatments have been adopted to obtain and preserve the τ-phase.

[0007] In many cases, the tau phase spontaneously decomposes, especially upon further processing, including, for example, deformation and / or elevated temperatures, making it difficult to obtain high-quality, high-purity tau phase. This is particularly problematic if one wants to obtain powders of alloys suitable for permanent magnets. Ideally, the particles forming the powder should be single crystalline and exhibit domain pinning. To this end, the material is usually milled. However, milling can require very small particles to arrive at single grain particles (resulting in low purity) and to magnetically align the particles to make them valuable. This can lead to problems associated with handling and compaction.

[0008] The powder therefore needs to be very fine, most preferably with only one grain (crystal) per particle, as this improves alignment and therefore magnetic remanence. However, the processing methods currently used to produce the alloy in powder form (such as ball milling) distort the structure and partially destroy the tau phase. Therefore, a method capable of producing nanoparticles with a high content of tau phase could facilitate the production of powders that can be more easily aligned while maintaining good magnetic properties.

[0009] As can be derived from Fig. 1, in a pure Al / Mn system, the τ phase can only exist between about 49 and 61 atomic % Mn, the rest being Al and unavoidable impurities. Moreover, the possibility of forming the τ phase in a binary composition of Mn and Al is maximum at 54-56 atomic % Mn, as shown by the dotted hyperbolic line in Fig. 2. At the same time, the theoretical magnetic moment of the material is higher for compositions with lower Mn content.

[0010] It has also been reported that the presence of dopants such as carbon or boron can stabilize the tau phase and promote the formation of alloys leading to improved saturation magnetization Ms. Furthermore, it has been reported that Ms increases with carbon. These advantages are partially balanced by disadvantages. For example, the Curie temperature and anisotropy field of doped alloys are lower than those of undoped alloys. Stoichiometric Mn 54 Al 44 C2, Mn 54 Al 44 B2, and Mn 54 Al 44 Further studies using carbon, boron and carbon-boron doped MnAl alloys of B1C1 and their behavior during mechanical milling steps are described in [1].

[0011] Considering the above, it is clear that most of the research carried out so far has been directed towards MnAl alloys with Mn content of 55 atomic % or less and with no or few dopants in order to obtain materials that maintain the τ-phase with high magnetic moment as well as the highest possible Curie temperature. 54 Al 46 The present study is the preparation of a τ-phase MnAl alloy having Mn 52 Al 48 and Mn 56 Al 44 Attempts to prepare the tau phase by strip casting of the composition Mn 52 Al 48 and Mn 54 Al 56 The τ phase of the strip-cast Mn 56 Al 44 It has been reported that Mn tends to form γ2 and β in other samples. All materials showed an increase in the amount of γ2 and β after grinding. The material with the highest saturation magnetization (Ms) was Mn 54 Al 46 The strip, i.e., before grinding, showed (at 5 Tesla) 114 emu / g (Wb m / kg).

[0012] H. Fang et al. 54 Al 46 and (Mn 0.55 Al 0.45 ) 100 reported that the τ-phase could be obtained by direct casting of C2 using a droplet synthesis method that involves rapid cooling of the melt from 1400 °C to room temperature in 10 min (see Non-Patent Document 3). Here, the highest Ms was obtained by casting C2 using a droplet synthesis method that involves rapid cooling of the melt from 1400 °C to room temperature in 10 min (see Non-Patent Document 3). 0.55 Al 0.45 ) 100 In the C2 system (at 9 T), 111 emu / g (Wb m / kg) was obtained.

[0013] The article further teaches that the crystal order in the MnAl system is important for magnetization, with an average of 10% of the Mn atoms occupying Al sites and interacting antiferromagnetically with Mn at the (0,0,0) sites, so that the excess Mn creates a "built-in" disorder. This is illustrated in Figure 2, where the "2%, "5%, " and "8%" lines show how the magnetic moment is affected by the amount of misplaced Mn, i.e., when 2%, 5%, or 8% of the Al sites are substituted by Mn atoms compared to the ideal case. The ideal case for a 55%Mn / 45%Al alloy is for 10% of the Al sites to be occupied by Mn atoms. Thus, for this composition, a 5% mismatch means that 15% of the Al sites are populated by Mn.

[0014] Fang further suggests that the stability field of the β phase is wider than previously expected, extending up to 46 at.% Al (corresponding to 54% Mn), especially for materials that are subsequently processed by mechanical treatments such as high-energy ball milling.

[0015] A comparison of τ-phase MnAl prepared via different routes is provided by [4], which also has the stoichiometric composition Mn 54 Al 46The material is gas atomized from the melt under argon and cast into ribbons using melt spin casting under argon or by pouring the molten alloy onto the surface of a cooled copper dish rotating at high speed under argon to form alloy droplets. The gas atomized material contained about 66% tau phase, with beta and gamma 2 also present. The document further states that heat treatment of the milled powder (i.e. the material obtained after gas atomization of the melt and its additional milling using a water-cooled Union Process 1SD Svegari attritor) causes the transformation of the epsilon phase into the tau phase, while the equilibrium gamma 2 and beta phases are still present in essentially the same amounts as before the heat treatment. It is further stated that in the milled material, the cooling rate of the powder appears to be so fast that no formation of high temperature phases occurs and beta and gamma 2 are formed directly from the melt. It is concluded that the tau phase does not form in this way, since it is transformed from the epsilon phase, not directly from the melt.

[0016] Therefore, the tau phase is usually prepared by transforming the ε phase. Various mechanisms have been proposed for transforming the ε phase into the tau phase, and in fact different mechanisms may be involved. In 2002, Yanar et al. showed that the transformation follows a compositionally invariant diffusion and growth process in a "large-scale" mode, which is transferred by incoherent interphase interfaces (Non-Patent Document 5). However, the transformation can also occur in a displacement mode.

[0017] One problem currently faced with such materials is that small particles of material are typically required for subsequent processing, and grain size reduction is desired to improve magnetic properties, potentially reducing the grain size to the size of a single magnetic domain. Such grain size reduction steps typically increase the coercivity (Hc), which is generally associated with an undesirable decrease in saturation magnetization (Ms). Another approach to obtain materials with improved coercivity is described by [6], by using high pressure compaction of melt-spun ribbons, which is believed to lead to grain refinement. The material before compaction was 122 Am at 8 T.2 The material had a high magnetization of 0.13 T (1.3 kOe) per kg and a low coercivity of 0.13 T (1.3 kOe), whereas the compressed material had a coercivity of 0.38 T (3.8 kOe) but a lower magnetization (45 Am 2 The authors also note that the Hc of the MnAl melt-spun ribbons is larger than that of the MnAlC melt-spun ribbons due to the presence of large amounts of impurities that may act as pinning centers for magnetization reversal.

[0018] It can therefore be derived from this literature that the amount of impurities such as carbon must be kept low to achieve high coercivity, but this ultimately comes at the expense of phase stability, resulting in low tau-phase purity and poor magnetic saturation, as discussed above.

[0019] Another mechanism for increasing the coercivity is to build up a high density of defects and a high level of internal strain without decomposing the metastable tau phase by using low-energy mechanical milling on the melt-spun ribbons, as described by [7]. The reported properties are a saturation magnetization of 62 Am 2 / kg and a coercivity of about 5 kOe. However, the strain is easily reduced when exposed to heat (which is often necessary for magnet production), with a corresponding loss of coercivity. Alternatively, powders can be used to produce bonded magnets, but here the magnetic saturation is inevitably reduced due to dilution of the magnetic material.

[0020] However, to be suitable for real-life applications, a material ultimately needs to have both high Ms and Hc, and the prior art cannot provide such a material since there is generally a trade-off between Ms and Hc.

[0021] It is another issue that crystal twins occur in the ε and / or τ phases. This phenomenon is discussed, for example, in the paper by Friedrich Schmidt et al., which describes the effect of hot extrusion of the crystal structure and the formation of crystal twins. Twin defects occur in the as-transformed samples (i.e. after transformation from the ε phase to the τ phase) but also in the subsequent hot extruded samples, to a substantially lesser extent. Another paper on the presence, formation and related issues of twins and anti-phase boundaries (APBs) is published in Friedrich Schmidt et al., which describes simulations that explain the experimental observations that samples containing many twins have a much lower coercivity and that a grain structure containing fine twins greatly reduces the squareness of the hysteresis loop, thereby lowering the maximum energy product to only 5% of the theoretical maximum.

[0022] Therefore, the presence of crystal twins and antiphase boundaries is considered to be very detrimental to the magnetic properties, since the orientation of the twin crystals may be antiparallel ("true twin"), so that the magnetic properties plateau and have the opposite direction. It is therefore desirable to avoid the formation of crystal twins and antiphase boundaries during the formation of the ε and / or τ phases, as this would improve the magnetic properties. [Prior art documents] [Non-patent literature]

[0023] [Non-Patent Document 1] Master's thesis by Timothy E. Prost (University of Nebraska-Lincoln, Dept. of Mechanical & Materials Engineering), 2012 [Non-Patent Document 2] Shao et al. “One step preparation of pure τ-MnAl phase with high magnetization using strip casting method” (AIP ADVANCES 7, 056213 (2017) [Non-Patent Document 3] H. Fang et al. Journal of Solid State Chemistry 237(2016)300-306 [Non-Patent Document 4] A. Chaturvedi et al. J. Phys.: Condens. Matter 26 (2014) 064201 [Non-Patent Document 5] Yanar et al. Metallurgical and Materials Transactions A, vol. 33A, pp. 2413-2423, August 2002 [Non-Patent Document 6] Si, P., Qian, H., Wang, X. et al. Journal of Elec Materi (2019) 48: 794 [Non-Patent Document 7] Lu, W. Niu J., Wang, T. et al. Journal of Alloys and Compounds (2016)675: 163 [Non-Patent Document 8] F. Bittner et al in Acta Materialia 101 (2015), pages 48-54 [Non-Patent Document 9] S. Bance et al in Acta Materialia 131 (2017) 48-56 Summary of the Invention [Problem to be solved by the invention]

[0024] The object of the present invention is to provide a material having improved magnetic properties, where "improved magnetic properties" means in particular a high magnetization Ms and / or a high coercivity Hc.

[0025] In a related aspect, it is an object of the present invention to provide a material having a high content (or high purity) and / or high quality of τ-phase, particularly (but not limited to) MnAl alloy material in powder or particle form. Here, the term "quality" includes in particular the aspects of the microstructural uniformity of the τ-phase, as well as the low site occupancy mismatch (i.e., ideal or near-ideal site occupancy by Mn and Al in the crystal lattice). The term "quality" also relates to the absence or low amount of crystal twins and / or reverse phase boundaries in the ε-phase and / or τ-phase.

[0026] The present invention also aims to provide a method by which such materials can be provided, in particular an industrially useful method.It is a further object of the present invention to provide an improved method for transforming the ε-phase to the τ-phase, thereby obtaining solid magnetic materials with improved magnetic properties.

[0027] Yet another object of the present invention is to provide a material based on Mn, Al, and optionally C, capable of forming τ-phase or ε-phase, which is relatively robust to further processing steps and / or changes in synthesis conditions, such as cooling rate from the melt, and still results in a high purity ε-phase and subsequently the τ-phase formed therefrom. In this specification, the τ-phase exhibits a preferred microstructure, which allows for materials with improved magnetic properties to be obtained.

[0028] Yet another object of the present invention is to provide an improved synthesis route that includes a preparation process that includes the appropriate composition of the MnAl alloy, as well as an appropriate quenching (cooling) rate from the melt to ensure a microstructure suitable for preparing high purity ε-phase and the subsequent τ-phase. The resulting material is particularly suitable for the subsequent micronization step that is known to exhibit a tendency to degrade the τ-phase.

[0029] It is a further object of the present invention to provide a material, preferably in particulate form, based on an alloy of Mn, Al and optionally C, which simultaneously exhibits both high magnetic saturation (Ms) and high coercivity (Hc), as well as a method for its manufacture.

[0030] It is a further object of the present invention to provide a method that can reduce the formation of undesirable crystal twins and / or reverse phase boundaries in τ-phase crystals and / or ε-phase crystals, and to provide a material that has a reduced tendency to form crystal twins and / or reverse phase boundaries in τ-phase crystals and / or ε-phase crystals.

[0031] It is a further object of the present invention to provide a micronization process that allows for particle size reduction, particle size reduction, and allows for randomization and uniformity of the microstructure while also allowing for suitable magnetic properties.

[0032] Another object of the present invention is to provide small crystals that exhibit no or few twin and antiphase boundaries. Providing such particles would allow a gentler pulverization process (which may lead to higher hardness and brittleness), thereby opening the possibility to work with relatively coarse powders with higher quality crystals for magnetization in an applied magnetic field. For example, powder alignment prior to the compaction process leads to improved magnetic properties in terms of higher magnetic remanence and coercivity.

[0033] It is also an object of the present invention to provide a means for increasing the stability of the tau phase during milling and to provide a material that requires fewer or gentler milling operations to achieve the same or similar domain pinning effect as obtained with currently used milling techniques. It is also an object of the present invention to provide a material that has a higher hardness and is able to withstand subsequent processing and manufacturing operations while still providing improved or identical magnetic properties compared to known alloys based on manganese, aluminum, and carbon.

[0034] In yet another aspect, it is an object of the present invention to provide a means for obtaining MnAl alloys containing tau-phase that have high magnetic saturation before the micronization process and preferably also have high magnetic saturation and coercivity after the micronization process. [Means for solving the problem]

[0035] All aspects of the present invention aim to provide materials and / or methods for their manufacture which either have preferred magnetic properties themselves or are preferred precursor materials for preparing materials having preferred magnetic properties.

[0036] The present invention specifically achieves one or more of the above objects through the following aspects. (Item 1) An alloy based on manganese, aluminum, and optionally carbon, and dispersed nanoparticles made of material X, wherein material X is different from manganese, aluminum, carbon, or a mixture thereof, and satisfies the following requirements: a. The melting temperature of material X is 1400°C or higher, preferably 1500°C or higher; b. Material X is a solid composite material containing a metal. (Item 2) The amount of dispersed nanoparticles made from material X is determined by the formula: Amount of dispersed nanoparticles (%) = [Weight of dispersed nanoparticles] / [Total weight of magnetic solid material including dispersed nanoparticles] × 100 % or less, preferably 10% or less, for example 5% or less, by weight, based on the total weight of the solid composite material containing nanoparticles, according to (Item 3) 3. The solid composite material according to claim 1 or 2, wherein material X is selected from the group consisting of metals, metal carbides, metal nitrides, metal borides, and combinations thereof, preferably material X is selected from the group consisting of transition metal carbides, transition metal borides, and transition metal nitrides, more preferably transition metal carbides. (Item 4) 4. The solid composite material according to any one of items 1 to 3, wherein material X is selected from the group consisting of vanadium carbide, zirconium carbide, titanium carbide, and chromium carbide, and titanium nitride, preferably vanadium carbide. (Item 5) The alloy present in the solid composite material has the following chemical formula I:

number

[0037] Further aspects and embodiments of the present invention will become apparent from the following detailed description. [Brief description of the drawings]

[0038] [Figure 1] Selected parts of the phase diagram of the Al-Mn system [Diagram 2] Schematic showing the relationship between theoretical magnetic moment and manganese content. Ideal occupation of lattice sites by Mn and Al (circles), 2% misplacement of Al sites by Mn (triangles), 5% misplacement of Al sites by Mn (squares) and 8% misplacement of Al sites by Mn (diamonds). A slight excess of manganese (relative to the ideal crystal phase) and minimizing reverse site occupancy results in a larger magnetic moment. The dotted hyperbolic line shows the probability of forming τ-phase. This shows that a nearly perfect τ-phase crystal (i.e. less than 2% Mn-Al site occupancy reversal) at high Mn content (~57 at%) can give the same magnetic moment as a slightly poorer quality (>8%) low Mn content crystal (~53 at%), thereby indicating that a lower level of misplacement at high Mn content is required if good magnetic properties are desired. [Diagram 3] XRD (left) and NPD (right) patterns of the material obtained in Example 1 before flash heating [Figure 4] XRD (left) and NPD (right) patterns of the material of Example 1 after 5 or 15 min of flash heating. a) and b) are shown after 2 h of cryomilling (CM), and c) and d) are shown after 4 h of CM. [Diagram 5] Magnetization versus magnetic field for the material of Example 1, specifically a) drop synthesis (DS), b) CM2 hr and CM4 hr, c) CM2 hr flash heating 1 min and 5 min, d) CM4 hr flash heating 1 min and 5 min, respectively. [Figure 6] DSC graphs of materials obtained according to Example 2 for a) (Mn54Al46)C0.76 (Example 2-B1) and b) (Mn57Al43)C2.14 (Example 2-A3). [Figure 7] Example temperature curve for heat treatment (step b) [Figure 8] Example temperature curve for flash heat treatment (step d) [Figure 9a] X-ray powder diffraction (XRPD) diagrams of two samples a) of different stoichiometric composition obtained after gas atomization from the melt, and d) of particles of the same stoichiometric composition prepared from particles of ε or τ phase after milling after flash heat treatment. The upper diagram in each of Figures 9a) to 9c) relates to the material of composition (Mn53Al47)C1.50 (Example 2-B6), and the lower diagram relates to the material of composition Mn57Al43C2.04. [Figure 9b] X-ray powder diffraction (XRPD) diagrams of two samples, b) of different stoichiometric composition obtained after heat treatment at 650 °C for 3 h under argon, and d) of particles of the same stoichiometric composition prepared from particles of ε or τ phase after milling after flash heat treatment. The upper diagram in each of Figures 9a) to 9c) relates to the material of composition (Mn53Al47)C1.50 (Example 2-B6) and the lower diagram relates to the material of composition Mn57Al43C2.04. [Figure 9c]X-ray powder diffraction (XRPD) diagrams of two samples, c) of different stoichiometric composition obtained after heat treatment at 1100 °C for 30 min under vacuum, and d) of particles of the same stoichiometric composition prepared from particles of ε or τ phase after milling after flash heat treatment. The upper diagram in each of Figures 9a) to 9c) relates to a material of composition (Mn53Al47)C1.50 (Example 2-B6) and the lower diagram relates to a material of composition Mn57Al43C2.04. [Figure 9d] The bottom shows the XRPD data of (Mn57Al43)C2.0 after gas atomization and cryomilling (milled ε-phase), and the top shows the XRPD of the same material, where a heat treatment was performed between the gas atomization step (step a) and the cryomilling step (step c) to transform the ε-phase into the τ-phase (step b). [Figure 9e] Shown are XRPD data for as-synthesized (gas atomized) alloys of compositions (from top to bottom): (Mn59Al41)C1.33, (Mn56Al44)C0.96, and (Mn57Al43)C2.14. [Figure 9f] 1 shows the XRPD of a sample made in accordance with the present invention with high tau-phase purity (content) after heat treatment at 1100° C. for 30 minutes ((Mn57Al43)C2.14 (bottom)), as well as the XRPDs of two samples with lower tau-phase content after heat treatment of powders having compositions outside the scope of formula (I) ((Mn59Al41)C1.33) (top) and (Mn56Al44)C0.96 (middle)). [Figure 9g] Extract of the XRPD of a sample with composition (Mn57Al43)C2.14, showing a slight excess of undissolved carbon forming Mn3AlC. [Figure 10] SEM (Scanning Electron Microscope) images of two samples with different stoichiometric compositions. Polished cross-sections of polymer-embedded powders were prepared according to Example 2. [Figure 11]XRPD of two samples with different stoichiometry obtained after heat treatment in argon at 1100 °C for 30 min. The top diffractogram represents the sample shown in Figure 10c (outside formula (I)), and the bottom diffractogram represents the sample shown in Figure 10d (within formula (I)). [Figure 12] XRPD of two samples with different stoichiometric compositions obtained after grinding and subsequent flash heating to 950° C. according to Example 2. The sample with a composition within the range of formula (I) shows a high content of tau-phase (bottom), while the opposite is observed for the sample outside the range (top). [Figure 13] XRPD of a sample with stoichiometric composition (Mn53Al47)C1.50 outside the range of formula (I). The sample was ground according to Example 1 and then flash heated to 950°C. [Figure 14] XRPD of the same sample as in FIG. 13, but the sample was pre-heat treated at 650° C. to obtain the tau phase before milling according to Example 1, and then flash heated to 950° C. [Figure 15] XRPD of a sample with stoichiometric composition (Mn57Al43)C2.04 within the range of formula (I). The sample was ground according to Example 2 and subsequently flash heated at 950°C in vacuum only. The magnetic properties of this sample are slightly inferior to the corresponding sample treated in argon at 950°C, as shown in the bottom part of Figure 12. [Figure 16] a) shows a polarized LOM photograph of a composite material according to the invention, and b) shows a LOM image of the corresponding reference material. The photographs show a finer crystalline grain structure of the composite material according to the invention, and also fewer typical twins indicating high image contrast between the grains. [Figure 17]a) shows an atomic force microscope image (AFM) on a sample of a solid composite material of the invention consisting of a MnAlC alloy to which vanadium carbide nanoparticles have been added during preparation. The nanoparticles are visualized as bright spots. b) shows a magnetic force microscope image (MFM) of the same area shown in Fig. 17a). In the areas where the nanoparticles are concentrated, the magnetic domain pattern becomes brighter and finer, indicating the presence of a material with a high proportion of small randomly oriented crystals with less tendency to twinning, thereby improving the magnetic properties. [Figure 18] a) shows the XRD peaks of three materials according to the invention with different amounts of vanadium carbide nanoparticles added to the MnAlC alloy. The XRD shows that the tau phase is present in high purity. Interestingly, the higher the amount of vanadium carbide nanoparticles, the higher the peak height, thereby indicating that the material with the higher amount of nanoparticles has a higher order of crystallinity. b) shows the reference XRD data of 95% pure tau (top) and epsilon (bottom) phases. [Figure 19] Figure 1 shows the PXRD data of the crushed as-synthesized composite material (black) and the corresponding reference material (grey). The composite material shows a higher purity of the tau phase. [Figure 20] 19 shows the PXRD data for the material of FIG. 19 after 3 minutes of cryomilling. The composite material shows a higher purity of the tau phase. [Figure 21] PXRD data for cryomilled (3 min) and heat treated (550° C. in argon for 30 min) material are shown. The composite material of the present invention exhibits a higher purity of tau phase and a lower amount of undesired non-magnetic phase. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0039] definition In the present invention, unless otherwise stated, all physical parameters are at room temperature (20° C.) and atmospheric pressure (10 5 It is measured in Pa.

[0040] As used herein, the indefinite article "a" denotes one as well as plural and does not necessarily limit the referenced noun to the singular.

[0041] The term "about" means that the amount or value in question can be at or near the particular value specified, generally within ±5% of the indicated value. Thus, for example, the phrase "about 100" indicates a range of 100±5.

[0042] The term and / or means that all or only one of the indicated elements is present. For example, "a and / or b" means "only a", "only b", or "both a and b". In the case of "only a", the term also covers the possibility that b is not present, i.e. "only a but not b".

[0043] The term "comprising" as used herein is intended to be non-exclusive and open-ended. Thus, compositions containing specific components may contain other components than those listed. However, the term also includes the more restrictive meanings of "consisting of" and "consisting essentially of". The term "consisting essentially of" allows for the presence of up to 10% by weight, preferably up to 5% by weight, of materials other than those listed in the respective compositions, and other materials may be completely absent.

[0044] Whenever a range is indicated in the present invention, it may be indicated by using a hyphen, such as "52-56," by using the word "from" instead of a hyphen, or by using the word "between," such as "between 52 and 56," including each of the end values ​​of the range, such that the range "52-56" includes the values ​​52 and 56. However, because these notations also encompass the entire set of values ​​within the range, these terms are used as shorthand for the term "52 to 56."

[0045] The variables x, y, and z relating to the alloy composition are based on a molar basis, where x and y are taken to mean x+y=100, and correspond to the atomic % of the MnAl alloy (when no carbon is present). x Al y C z (X) a , z, and a, when used, indicate the amount of carbon (if present), and nanoparticles made from material X, are expressed on a molar basis relative to x+y=100. All other percentages are by weight unless otherwise noted.

[0046] The particle size of composite particles is usually defined as D50 unless otherwise stated. D50 defines that 50% by weight of the particles are equal to or less than the indicated size as determined by laser light scattering. The particle size of nanoparticles is difficult to determine by laser light scattering and must be determined by transmission electron microscopy (TEM) observation and is expressed numerically as D50.

[0047] During the manufacture of the magnetic solid material of the present invention, a particular heat treatment may be performed within a particular temperature range and for a particular time period. As an example, "heat treatment at a temperature of 300-500°C for 1-3 hours" means that the alloy is held at a temperature in the range of 300-500°C for 1-3 hours. The time used to heat to a lower limit (such as 300°C) and cool below the lower limit is not taken into account in the specified heat treatment period. Furthermore, such heat treatment steps typically do not exceed an upper limit.

[0048] The numerical values ​​of the characteristics and properties of the materials used or produced in the present invention relate to values ​​obtained using the equipment and conditions used in the examples. In case of differences or discrepancies, the following conditions shall prevail.

[0049] The saturation magnetization values ​​given are Am measured at an applied magnetic field of 9 Tesla (at room temperature of 20 °C and 1 atm using a Physical Property Measurement System, PPMS, available from Quantum Design, Inc.) unless otherwise specified. 2 Units are / kg.

[0050] For saturation magnetization data measured at an applied field of 1.8 T (using a vibrating sample magnetometer, VSM), values ​​have been converted to correspond to 9 T measurements for comparison purposes based on conversion factors obtained from previous measurements where both instruments were used on the same sample.

[0051] The coercive force is calculated by setting the material density to 5100 kg / m 3 The density is specified in kA / m assuming that the mass of the mass is 1. This density can be assumed for any other desired conversion, such as when converting a volumetric parameter to a weight parameter.

[0052] In the present invention, whenever a content of a crystalline phase in % is mentioned, the respective value refers to the value obtained by XRPD analysis accompanied by the Rietveld technique as described in the Examples section 1.3.

[0053] In the present invention, the alloy can be represented, for example, by the following composition: Mn x Al y C z where x=52.0-59.0, y=41.0-48.0, x+y=100, and z=0.0-3.0. This can be represented by the formula (I) 0.x Al 0.y ) 100 C z Therefore, there are z atoms of C for every 100 atoms of Al and Mn combined.

[0054] The present invention relates to a composite material comprising an alloy, such as an alloy represented by formula (I), and nanoparticles made of material X. Such a composite material may comprise Mnx Al y C z (X) a where X represents the material of the nanoparticle, e.g., a metal, metal nitride, metal boride, or metal carbide. The variable "a" indicates the molar amount of X relative to the molar amounts of Mn, Al, and C (if present), as determined by the values ​​represented by x, y, and z (based on x+y=100). x, y, z, and a all relate to the relative molar amounts of the respective components. As an example, Mn x Al y C z (X) a A composite material represented by contains x moles of Mn, y moles of Al, z moles of C, and a moles of X. This is also true when X is a metal compound containing multiple elements or different elements in specific ratios, such as VC, in which case there are a moles of VC for x moles of Mn, y moles of Al, and z moles of C. Even though "a" is expressed on a molar basis, it can easily be recalculated to weight %, given the known molecular weights of X, Mn, Al, and C.

[0055] The present invention relates to a solid composite material comprising an alloy based on manganese, aluminum and optionally carbon, the solid composite material further comprising nanoparticles made of material X. The nanoparticles are dispersed in a matrix formed by the alloy and optionally other components. The solid composite material usually consists or essentially consists of MnAl alloys such as those represented by formula (I) and dispersed nanoparticles. This means that 90-100% or 95-100% by weight of the solid composite material may be formed, for example, by alloying the formula (I) with the nanoparticles. Each of the components is described in more detail below.

[0056] An alloy based on manganese, aluminum, and optionally carbon In the context of the present invention, an alloy based on manganese, aluminum and optionally carbon relates to an alloy consisting or consisting essentially of manganese, aluminum, optionally carbon and optionally unavoidable impurities, meaning that 95% or more by weight, such as 98% or more by weight or 99% or more by weight of the alloy is formed by manganese, aluminum and, if present, carbon.

[0057] The alloy based on manganese, aluminum, and optionally carbon must be magnetic or be a precursor material that can provide a magnetic material upon further processing. To this end, any alloy based on Mn, Al, and C described in the art can be used to form the composite material of the present invention.

[0058] In one embodiment, the manganese, aluminum, and optionally carbon based alloy conforms to formula (I):

number

[0059] In one embodiment, z is greater than 0, preferably greater than or equal to 0.1, such as greater than or equal to 0.5. z can also be less than or equal to 2.5, such as less than or equal to 2.2 or less than or equal to 2.0.

[0060] In one embodiment of formula (I), x=54.0-57.0, y=43.0-46.0, and y+x=100, where z is preferably 1.0-1.9. In one embodiment, x can be 56.5-58.5 and y can be 41.5-43.5, or x=57.0-58.0 and y=42.0-43.0.

[0061] In these and all other embodiments, the ratio of x to z (x / z) is preferably in the range of 60 or less, 55 or less, 50 or less, 45 or less, or 50 or less. The ratio of x to z can also be 26 or more, such as 26-33, more preferably 27-30, such as 28 or 29.

[0062] The alloy thus consists of Mn, Al and optionally C, as well as potentially unavoidable impurities. In this specification, the term "unavoidable impurities" includes any elements other than Al, Mn and C present in the alloy, and typically denotes impurities that originate from the raw materials used to produce the powder or are introduced during the manufacturing process. The total content of such impurities is typically equal to or less than 0.5% by weight, preferably equal to or less than 0.25% by weight, and more preferably equal to or less than 0.1% by weight, relative to the total mass of the alloy. Of course, nanoparticles of material X are not impurities in this sense.

[0063] Thus, the alloys of formula (I) have a composition capable of forming the ε-phase, which is the precursor of the magnetic τ-phase, and which, upon appropriate treatment, can form the metastable τ-phase.

[0064] In one embodiment, the alloy, such as the alloy of Formula (I), exists in the ε-phase at 80% or more, e.g., at 90% or more or at 95% or more. In another embodiment, the alloy, such as the alloy of Formula (I), exists in the τ-phase at 80% or more, e.g., at 90% or more or at 95% or more. The alloy can be formed by any method known in the art, but preferably, the manufacturing method described below can be used.

[0065] As outlined above, most of the attempts to prepare MnAl alloys containing large amounts of τ-phase have focused on materials with a Mn content of 55% or less relative to the sum of Al and Mn. Furthermore, attempts have been made to stabilize the τ-phase by adding carbon as a dopant, but these attempts have also been made in MnAl alloys with such Mn contents. So far, little attention has been paid to the production of MnAl alloys exhibiting a high content of Mn (e.g., 56 at.% or more, e.g., 56.5-57.5 at.%, relative to the sum of Mn and Al).

[0066] The present invention is based in one aspect on the discovery that a key step in the preparation of MnAl alloys with a high content of τ-phase is the preparation of MnAl alloys with a high content of ε-phase. The present invention further provides a method for preparing such MnAl alloys with a high content of ε-phase (e.g., 75% or more, e.g., 80% or more, 85% or more, or 90% or more) by using specific process conditions other than those used or suggested in the prior art, as described in more detail below.

[0067] The invention is based in another aspect on the surprising discovery that alloys with a high content of tau phase can be prepared from compositions consisting of a relatively large amount of manganese (56.0-59.0 atomic % of the sum of Al and Mn) and a small amount of aluminum (41.0-44.0 atomic % of the sum of Al and Mn) in combination with a specific amount of carbon represented by a value of 1.0 or more, 1.5 or more, but not more than 2.4, for example not more than 2.0, as defined below by chemical formula (II). Compositions meeting these requirements can surprisingly be processed to contain a high content of tau phase and thus provide materials with improved magnetic properties. The carbon content can be preferentially selected to be related to the amount of Mn such that the molar ratio of Mn / C is in the range of 26-36, more preferably 26-33, for example 28-30. At these preferred and more preferred carbon contents, the alloy is considered to be saturated with carbon dissolved in the alloy, so that the tau phase can be most effectively stabilized.

[0068] The present invention is in a further aspect based on the surprising discovery that particles of MnAl alloys having favorable magnetic properties can be prepared by a process involving specific grinding conditions at low temperatures below -20°C (also called cryomilling) and / or specific heating conditions at high temperatures of 900-1000°C for a relatively short time or up to 20 minutes (hereinafter also called "flash heat treatment"). If both are performed, the flash heat treatment is usually performed after cryomilling, but in one embodiment it can also be performed without such a step or any other heating to temperatures above 800°C after the particles are initially formed from the melt.

[0069] Flash heat treatment was initially developed for alloys of formula (II) intended for use in the formation of materials free of nanoparticles present in the composites of the invention and is described in co-pending European Patent Application No. 17 189 240.9 (not prior art to the present invention). It has now been found that such heat treatment is a very efficient method for improving the purity of the τ phase and, without wishing to be bound by theory, it is believed that in the case of such materials flash heat treatment is effective in reducing β- and γ2-impurities as well as in rearranging Mn and Al in the crystal lattice and repairing defects in the crystal structure, particularly those caused by milling operations (including but not limited to cryo-milling). Surprisingly, it has been found that in the case of composites of the invention containing nanoparticles made from material X, flash heat treatment is unnecessary and may sometimes even have a detrimental effect on the magnetic properties. Again, without wishing to be bound by theory, it is believed that the presence of nanoparticles made from material X avoids or reduces the amount of impurities and defects that would be removed or repaired by flash heat treatment. This indicates that in addition to having improved magnetic properties over the prior art, the process of the present invention may be economically advantageous since it does not require such a flash heat treatment to obtain good magnetic properties.

[0070] Alloy of formula (II) The Mn, Al, and C based alloy, in one embodiment, may conform to formula (II) as defined below:

number

[0071] In this specification, the term "unavoidable impurities" includes any elements other than Al, Mn, and C, and typically denotes impurities that originate from the raw materials used to produce the powder or are introduced during the manufacturing process. The total content of such impurities is typically less than or equal to 0.5% by weight, preferably less than or equal to 0.25% by weight, and more preferably less than or equal to 0.1% by weight, relative to the total mass of the alloy. Again, of course, nanoparticles of material X are not impurities in this sense.

[0072] Compared to the prior art alloys, the alloy of formula (II) combines a relatively high manganese content with a carefully defined carbon content. Without wishing to be bound by theory, it is believed that the interstitial sites of the ferromagnetic τ-phase are occupied by carbon, making the τ-phase more thermodynamically stable or preferred. Furthermore, again without wishing to be bound by theory, the combination of carbon with manganese in an amount of 56.0-59.0 atomic % (relative to the sum of Al and Mn) makes it possible to obtain a more homogeneous microstructure of the MnAl alloy in both the ε- and τ-phases (see FIG. 10). This homogeneous microstructure can be at least partially preserved during possible further processing steps, so that the alloy of formula (II) provides an improved precursor material for end uses.

[0073] Again, not wishing to be bound by theory, the addition of carbon at the octahedral interstitial sites (1 / 2,1 / 2,0) is believed to be an effective way to stabilize the tetragonal structure of the tau phase elongated along the c-axis. Carbon lowers the Curie temperature and increases the saturation magnetization (Ms), resulting in a larger magnetic moment. The increased stability due to carbon doping is believed to occur because the interstitials inhibit the diffusion of Mn and Al atoms.

[0074] This finding is truly surprising, since it was generally believed that when the addition of C exceeds its solubility limit, carbide precipitates would form at higher carbon concentrations that would act as nucleation sites for the equilibrium phase. What is surprising here is that a higher manganese content can dissolve even more carbon, thus increasing the stability of the tau phase. Moreover, the smaller carbon atom is believed to also improve workability and relieve internal lattice stresses.

[0075] Suitable magnetic properties of materials with high τ-phase content were obtained when the value of z, which represents the number of carbon atoms per 100 (Al+Mn) atoms, is greater than or equal to 1.5, preferably greater than or equal to 1.7, more preferably greater than or equal to 1.9. At the same time, the maximum value of z is less than or equal to 2.4, preferably less than or equal to 2.2, more preferably less than or equal to 2.1.

[0076] The value of x, which represents the number of manganese atoms per 100 (Al+Mn) atoms, is greater than or equal to 56.0, preferably greater than or equal to 56.5, more preferably greater than or equal to 57.0. At the same time, the value of x is less than or equal to 59.0, preferably less than or equal to 58.5, more preferably less than or equal to 58.0.

[0077] The value of y, which represents the number of aluminum atoms per 100 (Al+Mn) atoms, is selected to be the sum x+y=100. y is less than or equal to 44.0, preferably less than or equal to 43.5, more preferably less than or equal to 43.0, and at the same time is greater than or equal to 41.0, preferably greater than or equal to 41.5, more preferably greater than or equal to 42.0.

[0078] The value of z, which represents the number of carbon atoms per 100 (Al+Mn) atoms, is 1.5 to 2.4. Therefore, the lower limit of z is 1.5 or more, for example, 1.6 or more, 1.7 or more, 1.8 or more, or 1.9 or more. The upper limit is 2.4 or less, but can also be 2.3 or less, 2.2 or less, or 2.1 or less. These lower and upper limits can be combined in any manner, and in a preferred embodiment, the value of z is 1.7 to 2.2, more preferably 1.9 to 2.1.

[0079] The values ​​of x, y, and z can be adjusted by mixing the appropriate amounts of starting compounds (usually elemental manganese, elemental aluminum, and graphite) to produce the alloy. In the final alloy, the values ​​of x, y, and z can be determined by analyzing the relative content of the metals by appropriate techniques such as ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectroscopy) and LECO elemental analysis for C, N, P, and S, or Spark Optical Emission Spectroscopy).

[0080] Given the above relationship between the amounts of Mn and C, the ratio of x to z (x / z) is preferably 26 or more, more preferably 27 or more or 27.5 or more, even more preferably 28 or more, and preferably at the same time 33 or less, more preferably 32 or less or 31 or less, even more preferably 30 or less. By adjusting the relative amounts of Mn and C so that x / z falls within these ranges, it is possible to maintain good magnetic properties while maximizing stabilization of the τ phase. Without wishing to be bound by theory, it is believed that a lower Mn / C ratio, such as less than 26, may not completely eliminate the risk of the presence of excess carbon that may form Mn3AlC or the like upon heat treatment. This risk is further minimized if the ratio of Mn / C, i.e. (x / z), is adjusted to meet the above preferred and more preferred ranges.

[0081] Although it is possible to form the τ-phase directly from the melt, it is more common to first form the ε-phase, followed by the formation of the τ-phase by a suitable heat treatment.

[0082] Thus, in a preferred embodiment, the alloy of formula (II) has an ε-phase content of 80% or more, more preferably 85% or more, and even more preferably 90% or more, as determined by XRPD using Rietveld refinement, as described in Example 1.3.

[0083] Nanoparticles made from material X In addition to the Al, Mn, and optionally C-based alloy, the composite material of the present invention comprises nanoparticles made from material X. As used herein, the term "made from" indicates that material X forms 90% or more by weight of the nanoparticles, such as 95% or more by weight or 99% or more by weight, or even 99.9% or more by weight.

[0084] The term "nanoparticle" means a particle having a diameter (longest axis) of 1000 nm or less as determined by TEM measurement.

[0085] The presence of nanoparticles represents a major difference with prior art materials, which usually consist of MnAl or MnAlC alloys, where there is only one relatively homogeneous material and the aim was usually to transform all the material from the ε-phase to the τ-phase. In this respect, crystal defects such as twins and reverse phase boundaries can arise not only during the formation of the ε-phase but also when transforming the ε-phase to the τ-phase.

[0086] The formation of a crystalline phase usually proceeds from a very small crystalline domain or even a unit cell, which then grows by bonding additional atoms in an orderly fashion to the crystalline domain. This process is subject to defects, particularly when two initially separate crystals grow on top of each other, where the crystal lattices become intertwined, creating the problem of twinning. The possibility of forming such crystalline defects increases as the crystal grows larger.

[0087] Without wishing to be bound by theory, it is believed that the nanoparticles act as crystal growth inhibitors or growth barriers. This means that crystal growth is restricted and therefore many more small crystals with random orientation are formed compared to larger crystals that are more likely to form twins if growth is allowed to proceed without such inhibitors or barriers. This is confirmed in Figure 16a) and Figure 16b), which show polarized LOM images of a composite material according to the invention (top) and a reference material without nanoparticles. It is clear that the composite material has a much finer structure, i.e. many more small crystals compared to fewer large crystals. These many small crystals are much less likely to form twins, which can improve the overall magnetic properties of the material. This is especially true for the coercivity, as the nanoparticles are also believed to form pinning centers for magnetic domains that improve the coercivity of the material.

[0088] Surprisingly, it was also found that the addition of nanoparticles improves the purity of the tau phase as can be derived from Fig. 18a, which shows the XRD data of composites with different amounts of vanadium carbide nanoparticles after cryomilling (3 min) and subsequent heat treatment at 550 °C for 30 min in argon. As can be derived from the figure, the composites with nanoparticles show a high purity of tau phase, which is rather surprising and counter-intuitive. Here, the amount of nanoparticles is not given in wt.%, but rather the composition (Mn x Al y ) C z (X) a Note that the formula "a" refers to the relative molar amount of

[0089] Moreover, for materials without nanoparticles, a flash heat treatment is often necessary to obtain good magnetic properties, which reduces the amount of impurities, corrects the crystal defects of the material obtained after cryomilling, and improves the purity of the τ-phase. Surprisingly, we found that such a flash heat treatment is not necessary for the claimed composite material, since the purity of the τ-phase is already very high after the typical synthesis steps for forming the τ-phase, e.g., milling and subsequent heat treatment at 450-600 °C. As a result, in one embodiment of the present invention, the process for preparing the composite material does not include a step of heating the formed and optionally milled composite material into particle form to a temperature of 800 °C or higher.

[0090] Thus, the average particle diameter of material X particles, expressed as the number-average median Dn50 determined by TEM methods using image analysis, can be up to 1000 nm, but is typically less than 1000 nm, for example 800 nm or less, 600 nm or less, or 500 nm or less, but can also be as low as 400 nm or less, 300 nm or less, 200 nm or less, or 100 nm or less. There is no lower limit, but particles with very small particle sizes are usually difficult to manufacture and / or expensive to obtain. For this reason, the lower limit of Dn50 is typically 5 nm or more, for example 10 nm or more or 15 nm or more.

[0091] Preferably, the amount of particles (by number) made of material X with a diameter greater than 1000 nm is 10% or less, more preferably 5% or less, and even more preferably 1% or less, relative to the total number of all particles made of material X. Most preferably, the composite material of the present invention does not contain any particles of material X with a diameter (longest axis) greater than 1000 nm. It is worth noting that each of these upper and lower thresholds for Dn50 can be combined with the disclosure above regarding the amount or absence of particles with a diameter greater than 1000 nm.

[0092] The particle size number distribution is not particularly limited, but is typically unimodal.

[0093] Material X is distinct from Al, Mn, and C (or any mixture or alloy consisting only of Mn, Al, and C); a. The melting temperature of material X is 1400°C or higher, preferably 1500°C or higher; b. Material X contains metal Meet the requirements.

[0094] Requirement a. ensures that, when added in the form of pre-prepared nanoparticles, the alloys based on Al, Mn, and C (which typically have melting points in the range below 1300-1400 °C) can be melted without melting the nanoparticles. This ensures that the particles remain substantially intact during the preparation of the composite and as such are dispersed in a matrix that includes, consists essentially of, or consists of the alloys based on Mn, Al, and optionally C. Carbon, if present in the alloy, will "dissolve" and reside in interstitial positions in the alloy's crystal structure, and the nanoparticles will form a distinct phase.

[0095] Therefore, the melting point of material X is 1400°C or more, for example 1450°C or more, 1500°C or more, or even 1600°C or more or 1700°C or more. There is no particular upper limit, but it can be, for example, 3500°C or less, 3400°C or less, 3300°C or less, 3200°C or less, or 3100°C or less, for example 3000°C or less. In particular, when the nanoparticles are formed by in situ addition of carbide-forming nanoparticle precursor materials to a melt of aluminum, manganese, and optionally carbon, as will be explained later, it is believed that those materials with high melting points show a greater tendency to form carbides, but at the same time a tendency to form large particles in the mm range. When the composite material is prepared by adding preformed nanoparticles, the upper limit of the melting temperature is believed to be less relevant.

[0096] Requirement b. helps ensure compatibility with the alloy, since non-metallic materials such as glasses or oxides may not have the necessary wettability and compatibility with the alloy melt. Thus, material X must include a metal, and in one embodiment of the present invention, material X is not on an oxide. It should be noted that the term "metal" in this context includes, in addition to alkali metals, alkaline earth metals, semi-metals Si, B, As, Se, Ga, Ge, In, Sn, Sb, Te, Pb, Bi, and transition metals. Of these, the transition metals, silicon, and boron, are preferred in terms of cost and availability of stable high melting point species.

[0097] The material X is preferably 4.0 to 8.0 g / cm 3 , more preferably 5.0 to 6.8 g / cm 3 This facilitates the particles to have a density that allows them to be dispersed in alloys based on Mn, Al, and optionally C, which is particularly important when adding preformed nanoparticles to the composite formation process. If the density is too high, the particles may sink to the bottom of the melt, and if the density is too low, the particles may float to the top of the melt. By selecting particles with a density within the above range, dispersion of the particles can be achieved by premixing the particles with the manganese raw powder / flakes using appropriate stirring, or other dispersion techniques such as tumbling or shaking. The density is preferably between 5.0 and 6.8 g / cm. 3 in which case a more uniform distribution of the particles in the melt can be more easily achieved.

[0098] Material X may be a metal, such as a transition metal, for example vanadium. However, material X may preferably be a metal compound, such as a metal carbide, nitride, or boride. Taking into account their polar aspects, material X is preferably not an oxide and / or does not contain oxygen atoms. The preference for metal compounds over pure metals is based on the observation that pure metals may react with the components of the alloy, which is less likely to occur with metal compounds. For example, when vanadium metal is added to the composition, the presence of vanadium carbide precipitates has been observed in the resulting composite or alloy, respectively. The formation of vanadium carbide consumes carbon in the formulation, so that there is no longer carbon to stabilize manganese in the interstitial positions of the MnAlC alloy. Furthermore, the metal or its reaction products with the MnAlC alloy components may have a greater tendency to form agglomerates, thereby making good dispersion of the nanoparticles more difficult.

[0099] Thus, in one embodiment, material X is selected from the group consisting of metals, metal carbides, metal nitrides, metal borides, and combinations thereof, preferably material X is selected from the group consisting of transition metal carbides, transition metal borides, and transition metal nitrides, more preferably transition metal carbides. Preferred examples of X include vanadium carbide, zirconium carbide, titanium carbide, molybdenum carbide, chromium carbide, and titanium nitride, more preferably vanadium carbide.

[0100] However, the possibility of adding extra carbon to the melt to compensate for the carbon consumed to form well-dispersed nano-sized carbides (e.g., vanadium carbides) is also included in the present invention, especially in those embodiments in which the composite material is prepared by adding nanoparticle precursor materials. Nevertheless, it is believed that the particle size, particle size distribution, and particle distribution of the solidified composite alloy particles can be better controlled and optimized if they are added directly in the form of stable metal compounds.

[0101] Material X is preferably a hard material having the desired density, and in this regard, in a preferred embodiment, material X is selected from metal carbides, metal nitrides, and metal borides, and combinations thereof. The metal carbides, metal nitrides, and metal borides are, in one embodiment, transition metal carbides, transition metal nitrides, or transition metal borides, respectively. Preferred materials are selected from vanadium carbide, zirconium carbide, titanium carbide, titanium nitride, and chromium carbide. An additional advantage of the carbides is that they have good wettability by the melt of the alloy, thereby allowing them to be easily dispersed.

[0102] Nanoparticles made from material X are typically commercially available, for example from US Research Nanomaterials, Inc. However, they can also be prepared according to any technique known to the person skilled in the art.

[0103] The amount of nanoparticles is 15% by weight or less based on the total weight of the composite material. The amount can also be 13% by weight or less, 12% by weight or less, 11% by weight or less, preferably 10% by weight or less, 9% by weight or less, 8% by weight or less, 7% by weight or less, 6% by weight or less, or 5% by weight or less, for example 4% by weight or less or 3% by weight or less. Since even a small amount leads to an improvement of the microstructure and avoids or reduces the formation of twins, the lower limit is not particularly limited, but is preferably 0.1% by weight or more, 0.5% by weight or more, for example 1.0% by weight or more or 1.2% by weight or more.

[0104] In this respect, the alloys and nanoparticles contained in or of which the composite material consists or essentially consist are also intended to be understood as meaning (Mn x Al y ) C z (X) awhere x, y, and z are as defined above for formula (I) or as defined for formula (II), including all preferred embodiments or subranges thereof, and in each case x+y=100, and a is a number representing the molar amount of X that allows the nanoparticles to be present in the amount by weight represented above. It should be noted that the weight percentages above relate to the entire composite, which may or may not include other components other than the alloy and nanoparticles, but the molar amount of X when represented by "a" relates to the alloy of only Mn, Al, and optionally C. Thus, while typical values ​​of "a" are not particularly limited, the value of a in the above expression can be 20.0 or less, e.g., 15.0 or less, 10.0 or less, or 8.0 or less, e.g., 7.0 or less, 6.0 or less, or 5.0 or less, but is usually 0.01 or more, e.g., 0.05 or more, 0.10 or more, 0.15 or more, 0.20 or more, or 0.25 or more, e.g., 0.40 or more, or 0.50 or more. This applies both when the composite material includes other components other than the alloy and the nanoparticles, and when such other components are essentially or completely absent.

[0105] In this respect, the effect of nanoparticles is believed to be caused by their number, rather than by their amount in weight percent, since each particle is believed to act as an inhibitor of the undesired growth of crystals. Considering that the volume and weight contribution of larger particles exceeds their contribution in terms of number and surface area, it may therefore be preferable to use a small amount (in terms of weight) of fine particles compared to a large amount of larger particles. Thus, using small particles allows a lower total weight of nanoparticles to be obtained to obtain a similar number of particles (and correspondingly a similar number of distortions limiting crystal growth) compared to using large nanoparticles. Thus, larger particles should be present in a larger weight proportion. Since material X is typically non-magnetic, by using smaller particles, better magnetic properties of the composite can be obtained, as long as good dispersion can be achieved. Thus, a similar effect on crystal growth and avoidance of twinning can be obtained with 1 wt% nanoparticles with an average particle size Dn50 of, for example, 50 nm, compared to 5 wt% nanoparticles with a larger Dn50 of, for example, 300 nm. Nevertheless, the latter magnetic properties per unit mass may be preferred simply because the magnetic phase can take up a larger weight percentage of the composite. In theory, as long as the grains are of the same dimension or larger than the width of the domain walls (usually taken to be 3-5 nm), they can pin the motion of the domain walls in place with an applied magnetic field, thereby contributing to an increase in the resulting coercivity.

[0106] Thus, the presence of nanoparticles in the composites of the present invention leads to many favorable effects. These include, but are not limited to, a higher stability of the τ-phase during grinding, possibly thanks to the reduction of twinning and APBs, and a reduced requirement to perform harsh grinding operations, since the domain pinning mechanism originates instead from the nanoparticles and less from impurities and crystal strains that reduce magnet saturation (Ms). It was also observed that the composites may exhibit higher hardness and more brittle properties compared to alloys without nanoparticles, thus avoiding the introduction of defects / strains that would reduce Ms.

[0107] composite material The composite material of the present invention comprises a manganese, aluminum, and optionally a carbon-based alloy, and dispersed nanoparticles made from material X.

[0108] The composite material may also contain additives such as flow enhancers or lubricants, for example fatty acids or fatty acid salts such as magnesium stearate, or silica, or binders such as resins. These are usually added after the particles and nanoparticles consisting of or consisting essentially of the alloy have been prepared, which usually involves a high temperature processing step to form a melt of the alloy in which the nanoparticles are dispersed, and then the dispersion is processed to form particles, for example by gas atomization followed by (cryo)milling. The presence of such additives may facilitate further processing of the particles into shaped objects that can be used, for example, as magnets in electrical and electronic applications. Such shaped objects may have a size of at least 1×1×1 mm, or at least 1 mm, as explained below. 3 The volume of the slit may be 0.01 to 0.05.

[0109] However, the composite material may also consist only of the alloy and the nanoparticles or consist essentially of these materials, the alloy and the nanoparticles preferably forming 80% or more by weight of the composite material, such as 90% or more by weight, 95% or more by weight, or 98% or more by weight, such as 100% by weight.

[0110] The composite material of the present invention has the potential to simultaneously exhibit high Ms and Hc. In one embodiment, the saturation magnetization Ms of the composite material is 68 Am 2 / kg or more, e.g. 70Am 2 / kg or more, preferably 75Am 2 / kg or more, more preferably 80Am 2 / kg or more, and the coercive force Hc is 70 kA / m or more, for example 90 kA / m or more, preferably 95 kA / m or more, and more preferably 100 kA / m or more.

[0111] It is believed that by carefully adjusting the synthesis conditions, particularly by ensuring that fine nanoparticles are uniformly distributed throughout the alloy, the inventive concept can simultaneously achieve even higher Ms and Hc. Thus, the present invention also provides a method for producing a ferromagnetic alloy having an Ms of 100Am. 2 / kg or more, 110Am 2 / kg or more, 115Am 2 / kg or more, 120Am 2 / kg or more, 125Am 2 / kg or more, or 130Am 2 / kg, while at the same time having an Hc of 100 kA / m or more, 110 kA / m or more, 120 kA / m or more, 130 kA / m or more, or even 150 or 180 kA / m or more.

[0112] Manufacturing method for composite materials The method for preparing a composite material, such as a composite material containing the alloys of formulas (I) and (II), is not particularly limited, but it can be suitably and preferably prepared by the method described below, in which case particularly preferred properties can be obtained.

[0113] As is well known, synthesis parameters, i.e. melting temperature, quenching or cooling rate of the melt, affect the homogeneity of the microstructure of the alloy, and suitable parameters can generally be selected by a person skilled in the art based on common general knowledge and / or can look to the preparation conditions described in the examples. Therefore, it is preferable to select the synthesis conditions and subsequent process conditions of the material so that inhomogeneities are eliminated as much as possible.

[0114] In a first step, a composition is provided that includes a molten alloy of aluminum, manganese, and optionally carbon, and nanoparticles. This can be achieved, for example, by heating a raw material mixture that includes aluminum and optionally carbon to a temperature of 1000° C. or higher under a protective atmosphere, such as argon. It is then further heated until it reaches a target melting temperature that is well below the melting point of material X. Manganese and nanoparticles made from material X are then added to the melt, where they are dispersed in the melt.

[0115] The melt temperature is typically in the range of 1300°C or higher, preferably 1400°C or higher, more preferably 1450°C or higher, for example 1500°C or higher. The melt needs to be homogenous so that it is held in the molten state at high temperature for some time (e.g., 5-20 minutes or more) to allow good mixing and diffusion of the components mainly by thermal convection and / or bubbling of inert gas. The nanoparticles and manganese powder (or flakes) can be preferably pre-mixed and pelletized to facilitate efficient dispersion of the nanoparticles.

[0116] The melt containing the dispersed nanoparticles is then processed to form a solidified material. Depending on the cooling rate, either the ε-phase or the τ-phase can form directly from the melt. Typically, cooling rates higher than about 10° C. / sec result in the ε-phase, while slower cooling rates at temperatures below about 1000° C. can directly result in the magnetic τ-phase.

[0117] Therefore, rapid cooling from the melt is preferred if a high content of ε-phase is desired in the material obtained directly from the melt. A high cooling rate is preferred to ensure a homogeneous composition and microstructure (minimizing segregation) within the solidified material as well as to form a high purity ε-phase. In order to avoid the formation of more thermodynamically stable phases (especially β and γ2) and to obtain a homogeneous distribution of the raw materials, the average cooling rate between the melting temperature and about 1150°C is preferably 10 3 ° C. / sec or more, more preferably 10 4°C / sec or more, and even more preferably 10 5 °C / sec or more. Additionally, to promote the direct formation of alloys with a high content of τ-phase and inhibit the formation of, for example, β- and γ2-phases, the average cooling rate below about 1050°C and above about 650°C is between 10°C / min and 40°C / min, preferably between 15°C / min and 25°C / min, and more preferably about 20°C / min.

[0118] If the quenching rate and / or mixing of the components in the melt prior to atomization was insufficient, the material may show regions of different composition caused by microstructural changes of different crystallinity and may also show relatively large differences in composition between the regions / segregations. The regions of lower crystallinity show significantly lower Mn / Al ratios and also lower carbon contents due to the reduced solubility of carbon in the presence of low amounts of manganese. It was found that large differences in composition between these regions / segregations are undesirable as they may cause inhomogeneities at the microstructural level even in materials that have undergone further processing steps.

[0119] Furthermore, the cooling rate in a "natural cooling process" (e.g., as described by Fang in Journal of Solid State Chemistry 237 (2016) 300-306) depends on various factors, such as the shape (e.g., ingot shape) and volume of the alloy being cooled, the temperature of the atmosphere, etc. In this paper, the cooling process is described as exhibiting a cooling rate from 1400°C to room temperature in about 10 minutes, which corresponds to an average cooling rate of about 2.3°C / s.

[0120] This is because the natural cooling process, for example of an alloy cast from the melt to form an ingot, is usually too slow to form a pure ε phase with a uniform microstructure, but still too fast to directly form the τ phase. If a material with a high content of ε phase is desired, additional measures must be taken to achieve a higher cooling rate. These include, in particular, measures to increase the surface area relative to the mass of the melt, thereby increasing the cooling rate, and forced cooling, for example measures to form droplets from the melt in order to contact the molten alloy (preferably in droplet form) with a cooling medium such as a cooling substrate, a cooling gas, or a cooling liquid, e.g. water. Suitable methods therefore include gas or liquid atomization, melt spinning or rotational casting. Gas atomization is preferred because it is scalable, allows good orientation in a magnetic field, and produces approximately round or spherical particles that, after transformation of the ε phase into the final desired τ phase, require little or no further mechanical treatment, such as milling, to obtain a powder material suitable for further processing and end use. Furthermore, gas atomization is believed to exert little stress on the internal structure of the alloy during cooling, thereby promoting the formation of a relatively uniform crystal structure with many single crystal domains, so that gas atomized particles exhibit good uniformity and fewer crystal defects.

[0121] Cooling of the alloy containing dispersed nanoparticles from the melt (e.g. during gas atomization) is preferably carried out in an inert gas atmosphere such as argon or nitrogen to avoid oxide formation and maintain a uniform structure. Cooling of the droplets into a water bath can also be applied, which allows reaching even higher cooling rates, but results in higher oxygen content.

[0122] By providing a melt of MnAl alloy of formula (I) containing dispersed nanoparticles and carrying out a cooling process in an inert gas atmosphere or in water using a cooling rate fast enough to avoid substantial formation of impurity phases (e.g., β, γ2) or τ phases, a homogeneous, ε-phase-rich material can be obtained. This material, as obtained by gas atomization of the melt and cooling under inert gas or water conditions, is an excellent precursor material for further processing steps. However, for example, in the 10 5 or 10 6 Care should be taken to avoid extreme cooling rates above °C / sec, as this can interfere with the crystallization process and reduce the purity of the desired ε-phase.

[0123] It has further been found that the alloy composition of formula (II) is less sensitive to the synthesis conditions, in particular with regard to the quenching rate from the melt, and that due to its lower Mn content, a uniform microstructure can nevertheless be obtained under conditions which lead to less uniform / more inhomogeneous microstructures for alloys not according to formula (I). This is illustrated in the figures, in particular in Figs. 9 to 11, and will also be explained in more detail below in the description of step a. However, it is worth noting that the following effects are also considered to occur independently of the specific step of gas atomization (step a), i.e. without a step of gas atomization from the melt, but also for alloys of formula (II) produced by a different technique.

[0124] Figure 9a shows the composition Mn immediately after gas atomization, both under the same conditions. 53 Al 47 C 1.50 The diffraction diagram (XRPD) of the alloy is shown at the top, and the composition is Mn 57 Al 43 C 2.04The diffractogram of the alloy with the composition of formula (I) is shown at the bottom. As can be seen from the XRPD data, the top sample (within the range of formula (I) but not formula (II)) shows reasonably good purity, but some impurities (γ, β) are also present, as can be derived from the minor peaks around 42-43° 2θ. Such peaks are also present in the bottom diagram showing the diffractogram of the alloy with the composition of formula (I), but to a lesser extent.

[0125] What is interesting to note is also the difference in the homogeneity of the structure, as represented by the SEM pictures shown in Figures 10a) and 10b). Here, both samples show a microstructure composed of grains (dark in Figures 10a) and 10b)) and matrix phases (light in Figures 10a) and 10b)). Although both grains and matrix are mainly present in the ε phase, they differ in terms of their composition. The grains are formed in phase ε1, which has a high content of Mn and C, while the matrix is ​​formed in phase ε2, which has a high content of Al. The matrix region shows nanocrystalline nature, i.e. it has a low ability to crystallize.

[0126] Interestingly, the alloy according to formula (II) has a smaller difference in composition between the matrix and the grains compared to the alloy according to formula (I) (not formula (II)). Thus, the sample according to formula (II) has a more uniform microstructure. Without wishing to be bound by theory, it is believed that this difference in composition difference between the ε1 and ε2 phases is caused by the presence of a combination of carbon and a relatively large amount of Mn, resulting in a Mn / C ratio within the preferred and more preferred ranges mentioned above. Apparently, the presence of the required amount of carbon helps to avoid the formation of segregations, resulting in a more uniform structure.

[0127] This uniformity of the as-synthesized ε phase microstructure also influences the microstructure of the subsequently formed τ phase, as shown in Fig. 10c) and Fig. 10d). The sample according to formula (I) (but not formula (II)), which has a large microstructural heterogeneity, produces a highly heterogeneous microstructure consisting mainly of τ, γ2, and β when heated in vacuum at 1100 °C for 30 min (see Fig. 10c). Conversely, the sample according to formula (II) results in a much more uniform microstructure consisting mainly of τ phase (see Fig. 10d), which allows a higher Ms to be obtained.

[0128] This structural difference can also be observed in DSC analysis. Figure 6a) conforms to the chemical formula (I) (Mn 54 Al 46 ) 100 C 0.76 ) shows the DSC analysis of a sample that does not conform to formula (II). The DSC shows an exothermic peak around 522 °C, representing the formation of the τ-phase. Upon further heating, there are two endothermic peaks around 787 °C and 862 °C, representing the reformation of the ε-phase from the τ-phase. The occurrence of two distinct peaks in the DSC indicates that the formed τ-phase actually consists of at least two distinct subphases, one that transforms back to the ε-phase at about 787 °C and the other that transforms back to the ε-phase at about 862 °C. This is in good agreement with the structure observed in Figure 10c).

[0129] Samples according to formula (I) and formula (II) ((Mn 57 Al 443 ) 100 C 2.14 The DSC graph of ) is shown in Figure 6b. Here, there is one exothermic peak around 554 °C representing the formation of the τ-phase and one peak around 789 °C representing the reformation of the ε-phase. Notably, there is no peak at higher temperatures, as in Figure 6a), indicating that the microstructure is more homogeneous and essentially consists of only one τ-phase, which is in good agreement with the structure observed in Figure 10d).

[0130] Thus, an alloy composition of formula (II) having the right balance between Mn and C (i.e., having a proper Mn / C ratio) allows to obtain a more uniform ε phase and a more uniform τ phase compared to an alloy having a lower Mn content and / or an incorrect amount of carbon, i.e., an incorrect Mn / C ratio. Thus, the alloy of formula (II) is characterized in one embodiment by a DSC graph determined by a DSC method using a heating rate of 10°C / min from room temperature to 1300°C, which shows one endothermic peak of 15 J / g or more, preferably 25 J / g or more, more preferably 35 J / g or more, for example 40 J / g or more, in the temperature range of 780-810°C (or 780-800°C), and no endothermic peak in the temperature range of 840-880°C, or shows an endothermic peak of 5 J / g or less, preferably 3 J / g or less, more preferably 2 J / g or less in the temperature range of 840-880°C. This allows to form a more uniform τ phase. Although it is possible to obtain ε phase outside the composition of chemical formula (II), this ε shows a tendency to form not only τ phase but also more thermodynamically stable β and γ2 phases with appropriate heat treatment. Therefore, within the range of chemical formula (II), it is possible to obtain ε phase that is more suitable for obtaining higher purity and more uniform τ phase.

[0131] The composite material comprising the MnAl alloy of formula (I) or (II) can then be further processed after the formation of the ε-phase and / or τ-phase. For example, the τ-phase MnAl alloy of formula (I) or (II) (e.g. obtained by first forming the ε-phase and then transforming the ε-phase to the τ-phase by a suitable heat treatment) can be subjected to a grinding process. This grinding process can be a cryo-milling step at low temperature, but can also be another suitable grinding process known in the art, such as ball milling at another temperature, such as room temperature (20° C.).

[0132] Below, a more detailed description of the method steps of processing the composite material comprising nanoparticles and an alloy of formula (II) or (I) is given. In particular, the alloy of formula (I) can be prepared and processed differently, but is preferably also prepared and / or processed by the method of the present invention. For example, the alloy of formula (I) can be subjected to a gas atomization process from the melt, but it is possible to manufacture the starting material, for example, by strip casting.

[0133] Of course, in addition to the methods of the present invention described below, additional process steps may or may not be performed on the composite material.

[0134] Step i In this step, a composition is provided that contains nanoparticles and / or one or more nanoparticle precursors and a component of an alloy in the molten state based on manganese, aluminum and optionally carbon, the nanoparticles being dispersed within the molten alloy. For this purpose, the raw materials of the alloy (e.g. powders of manganese and aluminum and carbon in the form of carbon black, anthracite, pet coke or graphite) are usually provided and the raw materials are melted.

[0135] The raw materials for the alloy can be added simultaneously or subsequently, in one embodiment aluminum and optional carbon are added and heated, for example to above 1000° C., prior to the addition of manganese. As used herein, nanoparticles or nanoparticle precursors can be added before, together with, or after manganese.

[0136] In one embodiment, nanoparticles made from material X can be added to the raw materials prior to melting or can be added to the melt. The nanoparticles of material X are preferably premixed and pelletized with one of the metals, preferably manganese, before being added to the melt, as this is believed to facilitate the dispersion of the nanoparticles in the melt.

[0137] In another embodiment, a precursor material for nanoparticles can be added. This can be a metal that forms nanoparticles when the melt solidifies. As an example, it has been observed that the addition of vanadium to the melt leads to the formation of vanadium carbide precipitates with sizes in the nanometer range, so in this embodiment, the nanoparticles are only formed upon solidification. The precursor material for nanoparticles is preferably a metal, more preferably a metal capable of forming carbides. Examples of such metals include vanadium, zirconium, titanium, molybdenum, niobium, tungsten, and chromium.

[0138] The precursor material is preferably a metal capable of forming a carbide at a melting temperature of 1500°C or more, but not exceeding 3300°C, for example not exceeding 3200°C. It is believed that carbide-forming metals with higher melting points have too high a tendency to form carbides, which in turn leads to undesirable grain growth, thereby forming carbide precipitates in the mm range. Thus, the preferred precursor materials are vanadium, titanium, molybdenum, tungsten, and chromium, since their carbides exhibit melting points within the aforementioned ranges.

[0139] When adding metals capable of forming carbides, the amount of carbon added to compensate for reaction with the nanoparticle precursors must be adjusted to ensure that enough carbon remains to stabilize the desired τ or ε phase.

[0140] Of course, it is possible to add both nanoparticles and one or more nanoparticle precursor materials, but typically only one of these is added. Furthermore, it has been observed that the growth and distribution of nanoparticles formed from nanoparticle precursors can be difficult to control and can be more greatly affected by process conditions such as cooling rate, so the embodiment in which nanoparticles are added is preferred from a practical point of view.

[0141] Regardless of whether nanoparticles or one or more nanoparticle precursors are added, it is preferable to provide sufficient mixing and dispersion of the nanoparticles and / or precursors to distribute the nanoparticles present in the solidified material.

[0142] The temperature reached in this melting step is usually in the range of 1300°C or more, preferably 1350°C or more, more preferably 1450°C or more, for example 1500°C or more. The upper limit is set by the melting point of material X when adding nanoparticles. Preferably, the upper limit is 100°C or more lower than the melting point of material X. Processing in the range of 1400°C to 1700°C is usually sufficient to obtain a melt and also reduces losses due to evaporation. Therefore, the temperature can preferably be 1400°C or more to 1700°C or less. Heating can be performed by any means known in the art, but induction melting is preferred.

[0143] To obtain a homogeneous melt by thermal diffusion of the components, it is preferred to heat the material to a melt for a sufficient time, for example 5-20 minutes or more, at 1400° C. or higher, for example 1500° C.

[0144] Step i is preferably carried out under an inert gas atmosphere (eg argon or nitrogen) to avoid the formation of oxides.

[0145] Step ii. Processing into particle form In step ii, the composition resulting from step i is treated to form particles containing MnAl alloys with ε and / or τ phases. Again, preferably an inert gas is used. The particles obtained at the end of this step contain an alloy of aluminum, manganese, and optionally carbon, and nanoparticles made of material X dispersed within the alloy, regardless of whether preformed nanoparticles or one or more nanoparticle precursors were added in step i.

[0146] This step can be carried out by many methods known in the art, preferably gas or liquid atomization, more preferably gas atomization. The gas used for gas atomization is preferably oxygen-free and is preferably selected from argon, nitrogen, helium, and neon. The atomization gas is usually argon or nitrogen (pressure between 5 and 300 bar, more preferably between 10 and 100 bar, e.g. 20 bar).

[0147] The formation of particles by gas atomization has the advantage over other techniques for preparing alloy particles, such as the milling of cast ingots, that the stress on the alloy is low, which minimizes the disturbance of the crystal structure. This allows a more homogeneous material to be obtained. Furthermore, the particles obtained are approximately spherical, which is preferably suitable for many subsequent process steps and / or end uses. In particular, the round shape of the particles obtained allows for easier orientation in a magnetic field, which may be beneficial even after the milling step, since it allows for an increase in powder density and an improvement in powder flow, making alignment easier. Finally, the gas atomization process makes it possible to obtain a rapid cooling of the molten alloy, which avoids the formation of tau phase and results in particles with a high content (purity) of ε phase. This allows for particles with a high tau phase content in subsequent processing steps that transform the ε phase into tau phase.

[0148] Step ii can be applied to all MnAl alloys, including those with compositions within the range of formula (I), but is preferably used for MnAl alloys with compositions of formula (II), due to the fact that in such cases a very pure ε-phase is obtained, as shown in FIG.

[0149] Figure 9a shows the composition of Mn at the top just after gas atomization under the same conditions. 53 Al 47 C 1.50 The diffraction diagram (XRPD) of the sample is shown below with the composition Mn 57 Al 43 C 2.04As can be seen from the XRPD data, the top sample, which is within the range of chemical formula (I), shows reasonably good purity, but some impurities (γ2, β) are also present, as can be derived from the minor peaks around 2θ 42-43°. Such peaks are also present in the alloy with the composition of chemical formula (II), shown at the bottom, but to a lesser extent. Also interesting to note is the similarity of the particle-matrix structure as represented by the SEM photographs shown in Figures 10a and 10b. In particular, for the alloy according to chemical formula (II), the difference in composition between the particles and the matrix becomes smaller. This is reflected in the microstructure after high temperature treatment, as shown in Figures 10c and 10d.

[0150] Thus, gas atomization leads to a good product in terms of homogeneity and purity of the ε phase when using alloys with a low Mn content, but even better products are obtained when gas atomization is performed on alloys of formula (II) with a high Mn content of 56-59 (vs. 100 for Al and Mn).

[0151] The particle size obtained in step ii is not particularly limited and can be adjusted by the selected appropriate conditions. Typically, the powder obtained from the gas atomization process has a weight-average particle size (or particle diameter) D50 of 200 μm or less, preferably 150 μm or less, more preferably in the range of 30 to 80 μm, as determined by laser light scattering method.

[0152] Step III Heat Treatment To obtain a material with a high content of τ-phase and good magnetic properties, a heat treatment at 350-700 °C, preferably 400-650 °C or 400-600 °C, for example 450-550 °C, is carried out for a suitable time, for example 0.5-24 h, preferably 1-10 h, for example 2-4 h, for example 3 h. This is shown in Figure 9b, which shows the respective XRPD diagrams after 3 hours at 650 °C. This step is also preferably carried out under vacuum or under an inert gas such as argon. The microstructure after such treatment is very similar to the microstructure achieved immediately after atomization (Figures 10a and 10b).

[0153] As shown in Figure 9b, Mn 53 Al 47 C 1.50 The upper material, with a composition of 0.01g / g, has a high purity of about 87% tau phase. The magnetization at 9 T is 112 emu / g (Wb m / kg) at 9 T, which is a very good value.

[0154] Conversely, the composition Mn 57 Al 43 C 2.04 The material of formula (II), shown at the bottom of Figure 9b, actually has a lower purity of the τ phase, despite the high purity of the ε phase in the starting material. This is also reflected in the magnetic properties, as the sample had a still good but slightly lower magnetization of 109 emu / g (Wb m / kg) at 9 T.

[0155] Thus, the heat treatment as described above can transform a material having a lower purity of ε phase after particle formation into a material having a higher purity (and / or quality) of τ phase. As a result, the present invention also includes an embodiment in which a composition comprising an alloy of chemical formula (I) in which x' is less than 56, e.g., 55.8 or less, but 50 or more, preferably 54.5 or less and 52.0 or more, y' is greater than 44 but 50 or less, preferably 45.5 or more and 48.0 or less (where x'+y'=100), and z' is 1.70 or less and 0.10 or more, preferably 1.50-0.80, is gas atomized and then heat treated as described above. This allows for a material rich in τ phase and having a magnetization of 110 emu / g (Wb·m / kg) or more (at 9 Tesla).

[0156] If necessary, the material resulting from step a can optionally be subjected to further pulverization processing, which can include, for example, ball milling, e.g., cryomilling in step c.

[0157] Step ii.b. Cryomilling "Cryomilling" is a term used to grind materials at temperatures below -20°C, for example below -100°C, preferably below -150°C, and is defined as step ii.b in the claims. Herein, the composite material obtained after step i is ground at temperatures below -20°C, preferably below -100°C, more preferably below -150°C, and even more preferably below -180°C. From a practical point of view, it is most preferred to carry out cryomilling at the boiling point of nitrogen (-196°C) at atmospheric pressure.

[0158] The inventors have found that conventional grinding operations such as ball milling at room temperature induce the formation of defects in the crystal structure, leading to an increase in coercivity, while resulting in degraded magnetic properties, especially saturation magnetization. Without wishing to be bound by theory, it is believed that the ε to τ transition is highly dependent, i.e., on the nucleation of the τ phase in an intermediate phase with the ε phase, and thus a microstructure with a high surface-to-volume aspect ratio of both the grains and particles may be important to promote the formation of the τ phase. Results show that the rate of formation of the τ phase from the ε phase is much faster from small grain powder form than from coarse grain material in bulk form (such as an ingot).

[0159] The shape and surface morphology of the particles can be controlled by the type of grinding technique and the processing parameters. The optimal size, spherical shape, and smooth surface of the particles can aid or facilitate achieving the preferred magnetic alignment of the powder particles, for example in the compression tool before compaction. Such particles are better designed to respond and rotate more easily to an external magnetic field. The particles align along their c-axis (easy axis) in the magnetic field. The alignment is preferably performed inside the compression tool just before and / or during the compacting or molding movement. The aligned particles result in an improved remanent magnetization (Mr) of the magnet body, i.e., the magnetization left in the body after the external magnetic field is removed.

[0160] Gas atomized powders are observed to be more spherical and have a smooth surface compared to water atomized powders. Therefore, gas atomized powders are preferred because they can expose a higher degree of smooth spherical surface even after subsequent grinding operations. Optionally, the ground powders of any synthesis method can be subjected to a spheroidization method, for example, plasma spheroidization by Techna® Group.

[0161] The starting material for cryomilling can be particles obtained by gas atomization of a molten alloy containing nanoparticles.

[0162] Furthermore, the milling of brittle materials results in smaller and sharper particles compared to the milling of soft materials. On the other hand, the milling of soft materials results in relatively large particles or even flakes for the same energy input. The milling of softer materials often results in smaller grains, more stressed crystal structures, or even an amorphous state. This is a further reason why, in one embodiment, the method of the present invention includes cryomilling, preferably cryomilling of the composite material of the present invention, including the alloy of formula (I) or (II) containing the tau phase.

[0163] The hardness of the ε phase is significantly higher than that of the τ phase, so milling in either phase has a decisive influence on the final properties, and cryogenic milling makes the powder much more brittle, thus affecting the milling result in a similar way.

[0164] Thus, the starting material for cryomilling can be any composite material including an alloy of formula (I). The starting material can include ε or τ phase, preferably in a predominant amount (e.g., more than 50% or 70%, as determined by XRD, see section 1.3), and in one preferred embodiment is a material including τ phase. This material including τ phase can be obtained directly from the melt including the nanoparticles by employing an appropriate cooling rate as known in the art, in which case the particles already including mainly τ phase can be subjected to cryomilling without intermittent heat treatment steps. However, the material can be first processed to form particles including mainly ε phase, and an intermittent heat treatment step can be performed before cryomilling to transform the ε phase to the τ phase. This transformed material can then be cryomilled and then subjected to the heat treatment of step iii.

[0165] Thus, in one embodiment, the starting material for cryomilling can be a composite material mainly comprising the τ-phase of an alloy of formula (I) or formula (II) obtained by a cooling process with or without subsequent treatment to increase the content or purity of the τ-phase. However, it can also be an ε-phase containing MnAl alloy of formula (I) or (II). It can also be an ε-phase containing material of formula (II), where x' is less than 56, e.g. 55.8 or less, y is greater than 44, e.g. 44.2 or more, and z' is less than 1.7, optionally subjected to a further heat treatment at 350-700 °C for 0.5-24 hours as outlined above.

[0166] The milling technique can be freely selected from conventional milling techniques such as ball milling, jet milling, pin milling, or other high shear processes such as hot extrusion. In one embodiment, the cryomilling step uses ball milling with a ball to powder ratio (by volume) of 10:1 to 30:1 for a suitable period such as 1 to 30 minutes, preferably 2 to 10 minutes.

[0167] The grinding is preferably carried out under vacuum or under an inert gas atmosphere, such as under argon, to avoid the formation of oxides. The material is preferably ground, for example, to small particle diameters (expressed as weight D50 and determined by laser light scattering), for example 100 μm or less, preferably 50 μm or less, more preferably 30 μm or less, even more preferably 10 μm or less, even more preferably 5 μm or less, for example 3 μm or less. In order to minimize distortion and degradation of the structure, the cryo-milling is preferably carried out for as short a time as possible, but as long as necessary to obtain the required particle size and degree of pulverization and / or degree of amorphization of the crystals, which depends on the hardness of the material and the grinding equipment used. For example, the (cryo)milling is preferably carried out for not more than 10 hours, preferably not more than 5 hours, even more preferably not more than 4 hours, but not less than 30 seconds, often not less than 1 minute.

[0168] Powders prior to milling can be coated with small amounts (<0.1 wt%) of organic substances such as surfactants or fatty acids such as oleic acid, commonly known as surfactants to aid in milling. Without being bound by any theory, the additives can protect the surface from excessive oxidation and minimize agglomeration during milling caused by adhesive or electrostatic forces between particles.

[0169] Flash Heat Treatment Flash heat treatment refers to a heat treatment carried out on the composite particles at a temperature of 900-1000 °C for 0.5-20 minutes, preferably 5-15 minutes, more preferably 8-12 minutes. This step is also called "flash heating" or "flash heat treatment". Flash heat treatment can not only transform the ε phase to the τ phase, but also increase the purity of the τ phase by reducing the amount of undesired non-magnetic phases.

[0170] The inventors have found that the structural distortions caused by processing operations such as milling in pure alloys (without nanoparticles) can be at least partially reversed and that the purity of the tau phase is significantly increased by carrying out a flash heat treatment step as outlined above on particles of MnAl alloys of formula (I) or formula (II). This so-called "flash heat treatment" allows to obtain an excellent combination of high magnetic saturation and coercivity after the pulverization process used to form the particles. However, it has now been found that such a flash heat treatment is in fact not necessary for the composites of the invention containing nanoparticles, since the presence of the nanoparticles results in a high phase purity even without such treatment. This shows that the composites of the invention may not only achieve better magnetic properties, but may also be produced more efficiently. Nevertheless, the quality of the composite may be improved by flash heat treatment if there are alloy defects present during the initial preparation that lead to a decrease in the phase purity of the alloy present in the composite.

[0171] Flash heat treatment, if performed, is preferably carried out by first heating at a relatively moderate temperature, e.g., 200-500°C, under vacuum or reduced pressure to ensure desorption of water, oxygen, or oxygenated species. The particles can then be further heated either in vacuum or in an inert gas. In this regard, it is preferred to use high heating rates, e.g., 25°C / min or higher, in the range of 30-60°C / min, between 600-900°C, to maximize the time above the temperature at which the ε to τ transition occurs (860-900°C).

[0172] The temperature is then held between 900-1000°C for 0.5-20 minutes, preferably 5-15 minutes. It is preferable to keep the time as short as possible to limit grain growth and sintering of the particles. The appropriate time also depends on the surface area, the degree of crystal strain as induced by shear forces during pulverization, and the shape of the material; in many cases, 5-10 minutes is sufficient to form the tau phase.

[0173] The material is then typically cooled to room temperature. Again, the dwell time in the 600-900 °C temperature range is again kept as short as possible during cooling, so that the cooling rate is typically 25 °C / min or higher, such as in the range of 30-60 °C / min. By minimizing the time in the 600-900 °C temperature range, both during heating and cooling, the formation of impurities such as β and γ2 can be avoided or minimized.

[0174] Optionally, the pressure of the atmosphere at high temperatures (above 700° C.) can be increased to limit the loss of manganese and therefore the risk of forming non-magnetic impurities. This can be achieved by increasing the pressure of, for example, nitrogen or argon to more than 1 bar.

[0175] Starting material is preferably of a size and shape that does not require further processing.Therefore, starting material is preferably a particle having a small particle diameter, for example, 100 μm or less, preferably 50 μm or less, more preferably 30 μm or less, even more preferably 10 μm or less, even more preferably 5 μm or less (expressed as weight D50 and determined by laser light scattering method).

[0176] This flash heat treatment step results in the formation of the tau phase, which is due to the composition (Mn 57 Al 43 ) C 2.0 The XRPD data of the sample having the formula:

[0177] In the lower part of Figure 9d, the XRPD data of the sample obtained after gas atomization (step a, ε phase), cryomilling (step c, 6 min), and flash heat treatment (step d) are shown. In other words, the cryomilled ε phase was the starting material for the flash heat treatment. As can be clearly derived from the data, even if the starting material was mainly ε phase, the material after flash heat treatment is relatively pure τ phase. This material showed a magnetization of 77 emu / g (Wb m / kg) (at 9 T).

[0178] The top part of Figure 9d shows the same material with an additional heat treatment (step b) between the gas atomization step (step a) and the cryomilling step (step c) to transform the ε-phase into the τ-phase. In other words, the cryomilled τ-phase was the starting material for the flash heat treatment. The material obtained after the flash heat treatment also shows high purity of the τ-phase and a magnetization of 83 emu / g (Wb m / kg) at 9 T.

[0179] This indicates that the flash heat treatment step can provide particles with the desired shape with a high content and high quality of tau phase (as present in the particles as starting material). However, as outlined above, due to the presence of nanoparticles, flash heat treatment or another heat treatment at high temperature may not be necessary. As a result, in one embodiment, the temperature of the material does not exceed 700°C from the end of step i to the end of step iii. Thus, in one embodiment, the method of the present invention does not include a flash heat treatment as described above.

[0180] Method for forming shaped bodies, shaped bodies obtained thereby, and electric or electronic devices containing same - Patents.com The method of the invention typically delivers a composite material in particulate form, such that the composite material of the invention is in one embodiment present in a particular morphology, where the particles of the composite particles may have a median particle size by weight D50 of 5000 μm or less, more preferably 1000 μm or less, even more preferably 500 μm or less, even more preferably 100 μm or less, for example in the range of 10-100 or 15-80 μm, as determined by light scattering methods.

[0181] However, such particles are often not suitable for use as magnets in practical applications and in this regard should be at least 1×1×1 mm or at least 1 mm 3 In many cases, solid shaped objects with larger sizes, such as volumes of 100 mm or more, are needed. The shaped objects also need to have structural integrity to be able to be used, for example, in electrical or electronic equipment. Therefore, composite materials often need to be processed to form the shaped objects. For this purpose, any method known in the art can be used, such as extrusion, compression, additive manufacturing, plastic molding, etc.

[0182] Very often, binders and / or other additives may also be required to form the molded object and provide it with structural integrity and strength, while hot extrusion without additives (or only inorganic additives) is also conceivable. Such binders may, for example, comprise polymeric materials, thereby allowing for example extrusion of compositions comprising the composite material of the invention. Here, the polymeric materials may be selected from suitable materials, including common engineering plastics. These may, for example, be selected from olefin polymers such as PE, PP, polyisobutylene, polyesters, polyamides, polyurethanes, silicones, mixtures and copolymers thereof. In such compositions for forming molded objects comprising binders, optionally other additives may also be present, such as, for example, pigments, dyes, antioxidants, plasticizers, rheology modifiers, crosslinkers, etc. In such compositions for forming molded objects, and consequently also in the molded object itself, the relative amount of composite material may be 40% by weight or more, for example 50% by weight or more, or 75% by weight or more.

[0183] The shaped object then typically becomes a magnet that can be used in any application in which magnets are used. This includes, for example, magnets used in magnetic locks, signs, or magnets used to hold small items or graphical representations ("fridge magnets"), but also magnets used in electrical and electronic devices such as electric motors or computing devices such as computer hard drives. Further possible applications include speaker systems, earphones, or wind generators. EXAMPLES

[0184] The following Examples 1 and 2 relate to the manufacture and properties of MnAlC alloys and are therefore not representative of the claimed composite materials, which further comprise nanoparticles made from material X. These nanoparticles are not present in the materials of Examples 1 and 2, but are present in Examples 3 and 4, which illustrate the composite materials of the present invention. However, Examples 1 and 2 are provided to provide a better understanding of the synthesis of MnAlC alloys and the factors that affect their magnetic properties, particularly the saturation magnetization Ms and coercivity Hc, as well as the problems and pitfalls that arise in the absence of nanoparticles. EXAMPLES

[0185] 1.1 Sample synthesis 20g Mn 0.55 Al 0.45 C 0.02 The alloy ingots were synthesized by a droplet synthesis process starting from a melt at 1400 °C, similar to the synthesis method described in Non-Patent Document 3. All raw materials were of high purity, and Mn (Institute of Physics, Polish Academy of Sciences, 99.999% purity), C (Highways international, 99.999%), and Al (Granges SM, 99.999% purity) were used.

[0186] First, after evacuating the atmosphere and establishing a high vacuum (<0.001 bar), aluminum was heated and melted together with carbon black in an alumina crucible at 1000 °C. Subsequently, small pieces of Mn metal were tossed into the Al and C melt, and then the eddy current power was increased to allow the Mn pieces to react immediately with the Al-C liquid. The melt was maintained at 1400 °C for 10 min to ensure that the Mn-Al-C liquid formed a homogeneous alloy solution.

[0187] The Mn-Al-C alloy was cooled to room temperature by cooling the ingot in vacuum on a water-cooled Cu plate. The achieved cooling rate allows the direct formation of high-purity τ-MnAl in the alloy. The resulting material is also referred to below as the "drop synthesis" material.

[0188] 1.2 Cryomilling process Cryogenic milling was carried out at liquid nitrogen temperature (-183°C) using a SPEX Freezer / Mill® (6770). The starting material prepared above was placed in a stainless steel vial equipped with a stainless steel cylindrical impact member. The mass ratio between the impact member and the powder was 30:1. Before starting the milling, the vial was allowed to cool in the liquid nitrogen bath of the Freezer / Mill® for 30 minutes. Milling was then carried out at an impact frequency of 30 Hz for a total of 2 (CM2) or 4 hours (CM4). Each milling run consisted of a 5 minute milling and a 3 minute rest cycle.

[0189] Smooth spherical particle shapes are easiest to align along the easy axis of magnetization in a magnetic field. Cryomilling makes it possible to obtain particles that can undergo such easy alignment, since it does not result in the formation of randomly oriented sheet-like particles, as observed when milling is carried out at ambient temperature (see, for example, H. Jian et al., “Microstructure and magnetic properties of Mn-Al-C alloy powders prepared by ball milling” Journal of Alloys and Compounds 622 (2015) 524-428, or Z. Liu et al. “Structure and Properties Evolutions for Hard Magnetic MnAl and MnGa based Alloys prepared by Melt Spinning or Mechanical Milling”, Mater. Sci. Eng. Adv. Res 1(1) 12-19).

[0190] The smooth and spherical particle shape obtained by cryomilling was confirmed by visual inspection of the particles obtained after 2 and 4 hours of cryomilling using SEM imaging, where it was confirmed that the average particle size of the particles remained around 20 μm after 2 and 4 hours of cryomilling, respectively. The surface smoothness increased somewhat with longer milling times.

[0191] 1.3 Diffraction studies X-ray powder diffraction (XRD) was performed on a Bruker Twin-Twin diffractometer using Cu double Kα radiation (λ1=1.540598 Å, λ2=1.544390 Å). Neutron powder diffraction was performed in the JEEP-II reactor at the IFE (Institution for Energy), Kjeller, Norway. Neutron diffraction patterns were detected by a high-pressure neutron diffractometer. Crystal structure and phase analysis were processed by Fullproof software by the Rietveld method as described in H. Rietveld “A profile refinement method for nuclear and magnetic structures”, J. Appl. Crystal. 2(2) (1969). Peak shapes of the diffraction patterns were characterized by Thompson-Cox-Hastings pseudo-Voigt functions.

[0192] Cryomilled Mn for 2 (CM2) and 4 (CM4) hours when heated and cooled at different rates 0.55 Al 0.45 C 0.02 The phase transition behavior between the samples was investigated by in situ synchrotron X-ray diffraction at the P02.1 beamline of PETRA III (λ = 0.207 Å). 0.55 Al 0.45 C 0.02The sample was loaded into a single crystal sapphire tube, the tube was wrapped with Kanthal wire, heated in vacuum to 900°C (50°C / min), dwelled at 900°C for 5 min, and then cooled to room temperature (50°C / min). The temperature was monitored by a K-type thermocouple inserted from one side of the sapphire tube in close contact with the sample. The sample-to-detector distance and the wavelength of the X-ray beam were determined and calibrated by NIST LaB6 standard sample. X-ray diffraction patterns were recorded by a PerkinElmer XRD1621 fast area detector. The diffraction patterns of the 2D images were converted to 1D diffractograms by the Fit2D® program.

[0193] 1.4 Flash heating In the flash heating process, the samples were first placed into Al2O3 crucibles, which were then sealed into evacuated quartz tubes, and the ampoules were then transferred to a preheated resistance furnace and "flash heated" at 900 °C for a total of 1, 5, and 15 minutes, respectively, after which the ampoules were cooled in ambient air.

[0194] 1.5 Characterization of magnetic properties The powder samples were placed in gelatin capsules with varnish. Both the capsule and the varnish contribute to the paramagnetic moment at 300 K, accounting for less than 0.01% of the saturation magnetic moment at 9 T. The samples were measured on a Quantum Design Physical Property Measurement System (PPMS) equipped with a 9 T superconducting magnet or a Quantum Design MPMS. The magnetization in SI units and μB was calculated from the sample weight using the lattice constants obtained from the XRD / NPD refinement.

[0195] 1.6 X-ray and neutron powder diffraction Refined powder diffraction data of as-synthesized (Fig. 3a / b), 2 h cryomilled (2CM, Fig. 3c / d), and 4 h cryomilled (4CM, Fig. 3e / f) samples are shown in Figure 3 .

[0196] From the XRPD data (Fig. 3a, c, e), a clear decrease in peak intensity combined with significant peak broadening is observed at longer grinding times. Also, some weaker peaks (i.e., 1.73 Å and 1.89 Å) associated with the τ-phase (i.e., (001) and (100) and (002) planes) are observed. -1 , 2.27 Å -1 , and 3.47 Å -1 ) gradually disappears with longer grinding times. However, the remaining strong reflections from XRPD (i.e., 2.7 Å -1 ≦Q≦3.5Å -1 ) indicates that the crystalline phase has not yet been lost. Conversely, the NPD data (Fig. 3b, d, f) show a significant decrease in the reflection intensity for the 2CM sample, while no reflection is observed for the 4CM sample (Fig. 3f), reminiscent of an amorphous phase.

[0197] Combining the XRPD and NPD data (Figure 3) for the DS, 2CM, and 4CM samples, the lattice parameters for the space group P4 / mmm were refined. However, the NPD data was not refined for 4CM due to the absence of peaks. From Table 1 with the data obtained from the Rietveld refinement combining the XRPD and NPD data, it is found that the occupancy of Mn and Al sites changes with increasing milling time. After 2 hours of cryomilling, it is found that the Mn content at the Mn 1a (0,0,0) site decreases from 94% to 75% and the Al content increases from 6% to 25%. The opposite is observed at the Al 1d (1 / 2,1 / 2,1 / 2) site, where the Al content decreases from 85% to 66% after 2 hours of cryomilling (Table 2).

[0198] The refined XRPD patterns of the flash-heated 2CM and 4CM powders are shown in Fig. 4. It is clearly observed that the flash-heating process significantly recrystallizes the powders after only 5 min (Fig. 4a, c), producing peaks comparable to those of the original DS sample (Fig. 3a).

[0199] All XRPD patterns of the flash-heated samples contained predominantly -1 Although it contains detectable amounts of γ2 phase observed in (Fig. 4), the amounts of these phases are very small (<10%). A structural model with the same occupancies of Mn and Al as the DS sample indicates that rearrangement of Mn and Al at the two crystallographic sites occurs upon heat treatment (Table 1).

[0200] [Table 1]

[0201] The above results indicate that the flash heating process can reform the tau phase even after processing steps such as grinding that lead to the loss of previously present tau phase. These results are also consistent with the XRPD and NPD patterns shown in Figures 3 and 4, which show refined XRPDs of samples after cryomilling and flash heating: Figure 4a) after 2 hours of cryomilling and 900°C+5 minutes of flash heating, Figure 4b) after 2 hours of cryomilling and 900°C+15 minutes of flash heating, Figure 4c) after 4 hours of cryomilling and 900°C+5 minutes of flash heating, and Figure 4d) after 4 hours of cryomilling and 900°C+15 minutes of flash heating.

[0202] To further investigate the stability range of the τ-phase as a function of heating rate and temperature, 2CM samples were analyzed in situ by synchrotron radiation (λ = 0.207 Å). During the measurements, the powder was subjected to a heating rate of 50 °C / min from room temperature to 920 °C, held for 5 min, and then cooled again to room temperature at a rate of 50 °C / min. The 2CM powder was observed to decompose into a mixture of β and τ phases at about 500 °C. At T > 900 °C, the powder transforms completely into pure ε phase. However, during the cooling process at a cooling rate of 50 °C / min, the pure τ-phase reforms again at T < 830 °C.

[0203] The effect of the cryomilling process on the magnetic properties (i.e., Hc and Ms) was evaluated from measurements of magnetization versus magnetic field. From the magnetic hysteresis loops of the DS samples (see Figure 5a), the coercive field is

number

number

[0204] Overall, magnetization decreases significantly with increasing grinding time. After flash heating at 900 °C for 1 min, the Ms of 2CM and 4CM recover only to about 40% and about 19% of that of the original DS sample. However, the Hc is about 475% and about 750% higher than that of the original DS sample, respectively (see Table 2). Further increasing the flash heating time from 1 to 5 min at 900 °C, the 2CM and 4CM samples are about 88% and about 84% of the Ms value of the DS sample, respectively. However, the Hc values ​​of the 2CM and 4CM samples are only about 200% and about 300% higher than that of the original DS sample after flash heating at 900 °C for 5 min. Furthermore, heating for 15 min caused only minor changes, as shown in Table 2.

[0205] [Table 2]

[0206] The magnetic properties of the DS sample reveal that the Ms value of about 614.8 kA / m (about 120.5 Emu / g (Wb m / kg)) nearly reaches the theoretical limit of 676.4 kA / m, indicating that the ε-to-τ transition is nearly complete. Nevertheless, the Hc value is low at 40 mT, which may be insufficient for many industrial applications. In particular, Hc is significantly increased by cryomilling.

[0207] Without wishing to be bound by theory, it is believed that flash heating (in addition to minimizing impurities such as β and γ2 phases) is effective in rearranging Mn and Al within the crystal lattice and in particular repairing defects in this arrangement induced by the milling procedure. EXAMPLES

[0208] 2.1 Synthesis First, aluminum metal (Stena Aluminium AB, Sweden, >97 wt%) was melted together with graphite (Carbomax AB, Sweden, >98.5 wt%) in an argon atmosphere at a melting temperature of about 1100 °C. Manganese metal (Manganese metal company Ltd, SA, >99.7 wt%) was then added and the melting temperature was adjusted to 1400 °C and held there for 5 min before being gas atomized under an argon atmosphere at a pressure of about 19 bar. This resulted in rapid cooling of the gas atomized particles, forming an ε-MnAl alloy with high purity and low oxygen content (about 0.03 wt% for gas quenching). The raw materials were carefully adjusted to give the composition of the samples shown in Table 3.

[0209] 2.2 Crushing The gas atomized particles were then milled using a MM 400 mixer mill (Retsch GmbH) capable of dry, wet, or cryogenic milling, optionally under an argon atmosphere, using 50 mL hardened steel vials, 25 mm balls, a ball-to-powder ratio of 15:1, and an impact frequency of 30 Hz for 6 min.

[0210] The powder was pre-coated with 0.02 wt% oleic acid (as applied with vaporized acetone prior to milling). Before starting cryo-milling, the sealed vial was allowed to cool in a liquid nitrogen bath for 30 min. Between each 3 min of milling, the vial was allowed to cool again for 15 min. Cryo-milling was carried out under the conditions outlined above in section 1.2.

[0211] 2.3 XRD measurement XRD measurements were performed using a Panalytical X'Pert ProPW3040 multipurpose diffraction system equipped with an X-Celerator solid line detector. The experimental data were processed using Panalytical BV X'Pert HighScorePlus software version 4.0. The measurement conditions were: CuKα 0.15406 nm, accelerating voltage 45 kV, current 40 mA, Ni filter, 2θ scan range: 20-100°, divergence slit 0.5, time 30 min. Quantitative analysis by phase refinement was performed as described above in section 1.3.

[0212] 2.4 Magnetic measurements The samples were characterized for their magnetic properties using a LakeShore 7400 VSM (maximum applied field 1.8 T) and a Quantum Design PPMS (maximum applied field 9 T). The samples were placed in gelatin capsules and fixed with a weakly paramagnetic varnish (<0.01% of moment at 1.8 T). The magnetic field was 5100 kg / m 3 A density of was assumed.

[0213] 2.5 Differential Scanning Calorimetry (DSC) The melting and cooling behavior of the powders was measured using a simultaneous thermal analyzer (TGA and DCS) from Netzsch (Jupiter STA 449 F3) at 10°C / min up to 1250°C in argon gas with a sample size of approximately 40 mg.

[0214] 2.6 Scanning Electron Microscope (SEM) Particle samples were mounted on a fine mesh net with the addition of carbon CUF-4 and Bakelite PhenoCure®, ground and polished to 1 μm by standard processes. To improve the planarity, they were polished with OPS-S non-dried colloidal silica suspension for 5 min. The samples were subsequently etched with a diluted modified Keller's reagent containing 6 ml HCl, 33 ml HNO, 1 ml HF, and 290 ml H2O. To improve the surface conductivity, a thin layer of Au was sputtered onto the surface. The samples were analyzed with a field emission scanning electron microscope (FE-SEM) Hitachi SU6600 equipped with an electron discharge spectroscopy (EDS) system (Bruker EDX XFLASH 5010).

[0215] 2.7 Heat treatment High temperature treatment was applied to the as-synthesized powders or fragments either in vacuum or in argon, and the temperature profile is shown in Figure 7.

[0216] 2.8 Flash heat treatment of crushed powder Flash heat treatment was performed in a closed tube furnace (L 50 cm, φ 4 cm, Entech AB) using the temperature profile shown in Figure 8. First, the samples were degassed by repeatedly filling with argon and vacuum, then the temperature was slowly increased (10 °C / min) in vacuum. The vacuum was maintained at 350 °C until a low and stable pressure was reached. In the second stage, the temperature was rapidly increased (>40 °C / min) to 950 °C to perform the "flash treatment". The time above 900 °C was adjusted to about 8 min, followed by a rapid cooling to ambient temperature. In the second stage, the atmosphere was either vacuum or argon.

[0217] According to the above synthesis scheme, the following samples were prepared and subjected to DSC analysis.

[0218] [Table 3]

[0219] Of the above samples, sample named "2-B" does not conform to chemical formula (II), whereas sample named "2-A" conforms to chemical formula (II).

[0220] Figure 6 shows exemplary DSC graphs of the materials as synthesized above (Figure 6a: Example 2-B1, Figure 6b: Example 2-A3). The exothermic peak at about 450-550°C represents the martensitic transformation from ε-phase to τ-phase. At about 780-870°C, the ε-phase reforms, and at about 1170°C-1240°C, the alloy begins to melt.

[0221] The total area of ​​the peaks between 780 and 870 °C correlates with the amount of carbon-stabilized tau phase, and the total area covered by this / these peaks is shown in J / g in the table above. Here, a larger area value represents a larger amount of carbon-stabilized tau phase. However, in alloys containing up to 55% Mn, only up to 1.7% carbon can be dissolved. Increasing the amount of Mn allows increasing the amount of carbon, which in turn leads to a higher stability of the tau phase. Furthermore, when the Mn / C ratio is close to 28 (within the range of 26-33), i.e. for carbon-saturated or near-carbon-saturated tau phases, the carbon-stabilized tau phase is simply stable against further processing (grinding and heat treatment).

[0222] It is clear that when the requirements of formula (II) are met, a higher stability of the tau phase, i.e. a higher peak area in combination with a carbon-saturated tau phase (preferably Mn / C ratio between 28 and 30) is obtained.

[0223] Furthermore, from the above results, it is evident that the alloy according to chemical formula (II) exhibits only one peak in the DSC in the temperature range of 780-810°C (or 780-800°C), which is denoted as peak 1. This indicates high homogeneity of the τ phase, as only one obvious transition to the ε phase is observed.

[0224] The following additional observations were made, which indicate the importance of adjusting the composition of the alloy according to formula (II) and adjusting the Mn / C ratio.

[0225] Sample 2-B3 ((Mn 52 Al 48 ) C 2.36 ) has a high amount of carbon and a low amount of Mn. This sample contained a lot of undissolved carbon that formed carbides after heating to 550 or 1100 °C. This was confirmed by a significant peak of Mn3AlC in the XRPD (see also Figure 9g). Furthermore, the total peak area of ​​14.8 J / g indicates an amount of carbon dissolved in the tau phase of less than 1.87%, and the material is not stable upon heat treatment. Interestingly, the material does not show any DSC peak 1 in the temperature range of 780-810 °C, but only DSC peak 2 at higher temperatures.

[0226] Sample 2-B6((Mn 53 Al 47 ) C 1.50 ) contains just enough carbon to stabilize the tau phase, but too little Mn to fulfill the requirements of formula (II). As explained previously and shown in Figures 10a) and 10c), this sample has a somewhat inhomogeneous composition and, as a result, a non-uniform microstructure upon heat treatment, which has been shown to impair the magnetic properties.

[0227] Samples 2-B11 and 2-B12 have a high Mn / Al ratio but lack sufficient carbon. These samples were not stable at high temperature treatment and showed decomposition into β and γ2.

[0228] Sample 2-B5 also has a higher Mn / Al ratio and sufficient carbon, however, this sample is at the limit where tau phase may form, favoring the formation of beta phase and compromising the purity (and therefore magnetic properties) of the tau phase.

[0229] The above results show that a desirable balance of properties including, inter alia, high purity of the ε phase and high stability and purity of the τ phase, material stability to high temperature processing, good magnetic properties, and improved uniformity at the microscopic level can be simultaneously obtained by tailoring the composition of the MnAl alloy within the boundaries of formula (II) and its preferred embodiments. EXAMPLES

[0230] 3.1 Nanoparticles and Mn 55 Al 45 C 2 Synthesis of a composite material containing an alloy represented by First, aluminum metal (Stena Aluminium AB, Sweden, >97 wt%) was melted together with graphite (Carbomax AB, Sweden, >98.5 wt%) in a protective argon atmosphere at a temperature of about 1100 °C. Afterwards, about 2 / 3 of the manganese metal (Manganese metal company Ltd, SA, >99.7 wt%) was added and the melt temperature was adjusted to 1500 °C. Then, premixed pellets consisting of the rest of the powdered manganese and nanoparticles of vanadium carbide (99.9%, particle size 80-100 nm, INSCX exchange) were added to the melt to achieve the desired composition. The melt was then held there for 5 min before being gas atomized under an argon atmosphere at a pressure of about 19 bar. This resulted in the rapid cooling of the gas atomized particles, forming an ε-MnAl alloy with high purity and low oxygen content (about 0.03 wt% for gas quenching). The gas-atomized particles were cryomilled for 3 min and then heat treated at 550 °C for 30 min.

[0231] The following observations were made:

[0232] It was observed that in the presence of nanoparticles, materials with a high content of ε phase can be obtained even with small amounts of manganese (i.e., materials of formula (I) with x between 52.0 and 53.5 and y between 48.0 and 46.5). In the absence of nanoparticles, such small amounts of manganese do not result in materials with a high content of ε phase, but rather the formation of larger amounts of undesired phases such as γ2 and β. Thus, the presence of nanoparticles allows to obtain materials with a high content of ε phase that can later be transformed to τ phase, when otherwise only materials with a low content of ε phase (and a low content of τ phase after the later transformation) would be obtained. This shows that the formation of nanoparticles has a stabilizing effect on the desired phases ε and τ, exposing a way to reduce the amount of dopants (such as carbon) required to obtain otherwise stable phases. The possibility to reduce the amount of dopants such as carbon may then lead to improved magnetic properties.

[0233] Furthermore, gas atomization allows for good dispersion of nanoparticles in the resulting material, with the distribution of nanoparticles being observed to be more uniform than in the case of sample preparation by ingot formation and crushing as described below in Example 4. Therefore, gas atomization is believed to be the preferred method for obtaining materials with a more uniform distribution of nanoparticles, which may facilitate obtaining improved magnetic properties. EXAMPLES

[0234] 4.1 Manganese by induction melting at 1400-1500℃ 55 Al 45 C 2 (VC) y Synthesis of (y=0, 0.25, 0.5, 1, 3.5, 19) ingots (total of about 15g) High purity raw materials were used: Mn (X-Mn powder from Hoganas AB, lot 2112625, purity 99.9%), Al (Granges SM, purity 99.999%), C (Highways International, 99.999%), and VC nanopowder (high purity VC nanopowder from INSCX exchange, purity >99%, size 80-100 nm).55 Al 45 C2(VC) 0.25 indicates that the relative compositions are 55 atoms of Mn, 45 atoms of Al, 2 atoms of C (as part of a MnAl alloy), 0.25 atoms of V, and 0.25 atoms of C (as part of vanadium carbide, material X).

[0235] First, Mn and VC powders were weighed, thoroughly mixed, and pressed into pellets in an argon-filled glove box. Appropriate amounts of Al and C were mixed together with the Mn / VC pellets and loaded into an Al2O3 crucible. Then, it was transferred to a high-frequency induction furnace and the vacuum pump was operated for 1 h. Melting was performed in a high-purity argon atmosphere (400 mbar). When the liquid state was reached, the temperature was maintained for 1-3 min to form a homogeneous solution. Finally, the furnace was switched off and the mixture was naturally cooled to room temperature (about 5 h). The total mass loss during the synthesis was less than 2 wt%. To improve the homogeneity, the melting procedure was repeated 2-3 times, with the ingot being rotated in between. The obtained material is also referred to below as "induction melted" material.

[0236] The ingots were crushed and then cryomilled for 3 or 6 minutes, respectively, according to the procedure described in Example 2. The materials were heat treated under the heat treatment conditions shown in Table 5. The as-crushed, as-milled, and crushed and heat treated powders were analyzed according to those described in Example 2. However, the magnetic results were measured with a modified Epping M-meter reaching 1.5 T. The results are summarized in Table 4.

[0237] [Table 4]

[0238] Samples 4.1 and 4.2 are reference powders without nanoparticles. The data show that the trade-off between magnetic saturation and coercivity depends on which heat treatment is applied, i.e., a heat treatment at 550°C gives high coercivity but poor magnetic saturation due to the large amount of non-magnetic impurities. Conversely, applying a flash treatment at about 950°C restores purity but reduces coercivity. This is a typical example of the impurity-induced coercivity mechanism, which is widely known in the literature. On the other hand, a time-limited flash treatment allows the skilled person to optimize the properties to achieve the best possible combination.

[0239] Sample 4.3 shows the magnetic properties of a material cryomilled (6 min) and subsequently heat treated at 550 °C. Note that the magnetic saturation (Ms) and remanent magnetization (Mr) are significantly higher than the reference, yet still reach acceptable coercivity. Increasing the amount of well-dispersed nanoparticles increases the coercivity without significant loss of magnetic saturation. Sample 4.4 shows that flash treatment is not necessary for nanoparticle-containing composites with relatively pure alloys.

[0240] Samples 4.5 through 4.8 show the magnetic properties of the as-synthesized powders (gently crushed ingots). Reference samples containing no nanoparticles are compared to those of similar composition but containing 0.25, 0.5, and 1.0 molar parts of nanoparticles, respectively. The data show that the nanoparticles facilitate reaching higher magnetic saturation (and therefore higher tau-phase purity). XRD data for the crushed as-synthesized (neither milled nor annealed) material is shown in Figure 20, as well as the reference material containing no nanoparticles (Mn 55 Al 45 C2) is shown by the lower line (light grey) and the corresponding composite containing 1.0 molar part of VC nanoparticles (Mn 55 Al 45 C2(VC) 1.0) are shown above (black). It is clear that the relative peak intensity of the τ-phase is higher in the composite, indicating a high purity of the τ-phase already immediately after the first synthesis step without further treatment.

[0241] Samples 4.9 to 4.12 show the magnetic properties of the as-milled powders (cryomilled for 3 min). The reference sample without added nanoparticles shows lower magnetic saturation and, as a result, higher coercivity. However, the corresponding composite with 1.0 molar part of VC nanoparticles shows relatively high magnetic saturation and good coercivity. It should be noted that the coercivity is relatively high considering the tau-phase purity by XRD (see Figure 21). In Figure 21, the reference material without nanoparticles (Mn 55 Al 45 C2) is shown by the lower line (light grey) and 1.0 molar part of VC nanoparticles (Mn 55 Al 45 C2(VC) 1.0 ) are shown above (black), and the corresponding composites containing ZnO (CuO) and ZnO (DuO) are shown above (black), after 3 min of cryomilling, respectively.

[0242] Table 5 also shows the magnetic properties of the powders after cryomilling (3 min) and heat treatment (550 °C, 30 min argon) for Samples 4.13 to 4.16. It is clear that the magnetic saturation of the nanoparticle-containing composite powders is significantly improved, which is also confirmed by the XRD data. Even though the coercivity of the nanoparticle-containing sample is lower compared to the reference (Sample 4.13), the overall magnetic performance of the composites with nanoparticles is better. It is noted that Mr and Hc increase with increasing VC content. In the following Table 5, samples with different nanoparticle contents are also compared.

[0243] [Table 5]

[0244] As can be seen above, the saturation magnetization Ms is improved even with a small amount of vanadium carbide (VC) nanoparticles, and the remanent magnetization Mr increases with increasing nanoparticle content.

[0245] By the way, the composition Mn 55 Al 45 C2(VC) 3.5 The magnetic properties of sample 4.17 in did not confirm any further improvement of the magnetic properties with increasing nanoparticle content. However, here it was observed that the dispersion state of the nanoparticles was not optimal and there were nanoparticle agglomerates. It is therefore believed that the magnetic properties of this material could be further improved by adjusting the process conditions to obtain a better distribution of the nanoparticles throughout the composite, for example by using gas atomization instead of ingot crushing to form the particles.

[0246] Figure 22 shows the XRD data of the material obtained by cryomilling (3 min) followed by heat treatment at 550 °C for 30 min in argon, again revealing that the composite (Mn 55 Al 45 C2(VC) 1.0 ) is shown in black, and the reference material (Mn 55 Al 45 C2) is shown in grey. It is clear that the composite exhibits a higher τ-phase purity. The peak height intensity ratios of γ2(122) / τ(011) are 0.38 and 0.16 for the reference and composite, respectively. The average crystallite size of the τ-phase is calculated to be about 28 nm for the composite and about 35 nm for the reference, based on the Scherrer broadening of the (011) peak.

[0247] This is also confirmed by the polarized optical microscope photograph shown in Figure 16, where the composite with nanoparticles (1.0 molar equivalent) shown at the top contains significantly smaller subgrains and significantly less crystal twinning, which is known to be detrimental to magnetic properties.

[0248] Also, atomic force microscopy (AFM) and magnetic force microscopy (MFM) measurements were performed on an area of ​​50 × 50 μm, which, according to AFM, contained areas with a high local concentration of VC nanoparticles as well as areas with fewer VC nanoparticles. This is shown in Figure 17a (AFM) and b (MFM). The areas with many VC particles show a rather fine domain pattern (see the lower right quarter of the image). Conversely, in areas with fewer VC particles, the domain size is significantly larger. It is known that small magnetic domains with pinned defects can withstand a higher applied external magnetic field before domain wall migration occurs compared to the larger domains that are typically present in larger, defect-free grains (Magnetic Domains, Hubert A., Schafer R., ISBN 3-540-64108-4, 2000). This may therefore explain the improved magnetic properties of the composite material of the present invention.

[0249] Furthermore, the composites of the present invention can be produced without the need to rely on flash heat treatment, making the materials easy to prepare. Samples 4.17 to 4.20 show the magnetic properties after flash treatment at 950 °C on cryomilled (3 min) samples. It is clear that only a gentle grinding followed by a low temperature heat treatment or relaxation treatment can give materials with superior magnetic properties compared to the corresponding samples without nanoparticles.

[0250] surface hardness Surprisingly, it has been found that even small amounts of nanoparticles can provide a composite material with a higher hardness as a corresponding reference alloy without nanoparticles.

[0251] The surface hardness of the two samples shown below indicates that the composite containing VC nanoparticles has a significantly higher hardness. It is suggested that the relatively small grains observed in this sample are the reason for the higher hardness, although nanostructural reinforcement may also contribute to the higher strength (i.e., similar to precipitation hardening in metallurgy).

[0252] Higher hardness is usually associated with higher brittleness and may help improve the milling efficiency of these composite powders giving relatively small particles with less induced strain and crystal defects compared to their undoped counterparts.

[0253] [Table 6]

[0254] The surface hardness of these two samples indicates that the hardness of the composite is considerably higher. The higher stability of the tau phase combined with the higher brittleness may contribute to reaching improved magnetic properties of the final molded and processed magnetic parts.

[0255] The present invention provides a novel method and a novel composite material suitable for magnetic applications, and is therefore industrially applicable.

Claims

1. A solid composite material, 90-100% by weight of the solid composite material being formed by dispersed nanoparticles made of manganese, aluminum, and optionally a carbon-based alloy, and material X; said dispersed nanoparticles being particles having a diameter (longest axis) of 1000 nm or less as determined by TEM measurements, said dispersed nanoparticles being dispersed in a matrix formed by said alloy and optionally other components; The material X is different from manganese, aluminum, carbon, or a mixture thereof and satisfies the following requirements: a. The melting temperature of the material X is 1700°C or higher; b. The material X includes a metal. and meet, solid composite materials.

2. The amount of dispersed nanoparticles made from material X is Amount of dispersed nanoparticles (%)=[weight of dispersed nanoparticles] / [total weight of solid composite material containing dispersed nanoparticles]×100 2. The solid composite material according to claim 1, wherein the nanoparticles are present in an amount of 15% by weight or less, based on the total weight of the solid composite material including the nanoparticles, according to the formula:

3. 3. The solid composite material of claim 2, wherein the amount of the dispersed nanoparticles made from material X is less than or equal to 5 wt. % based on the total weight of the solid composite material including the nanoparticles.

4. The solid composite material according to any one of claims 1 to 3, wherein said material X is selected from the group consisting of metals, metal carbides, metal nitrides, metal borides, and combinations thereof.

5. A solid composite material according to any one of claims 1 to 4, wherein said material X is selected from the group consisting of transition metal carbides, transition metal borides and transition metal nitrides.

6. A solid composite material according to any one of claims 1 to 5, wherein said material X is selected from the group consisting of vanadium carbide, zirconium carbide, titanium carbide, and chromium carbide, and titanium nitride.

7. A solid composite material according to any one of claims 1 to 6, wherein said material X is vanadium carbide.

8. The alloy present in the solid composite material has the chemical formula I: [0010] A solid composite material according to any one of claims 1 to 7, having a composition:

9. 9. The solid composite material of claim 8, wherein x=54.0-57.0, y=43.0-46.0, and z=1.0-1.

9.

10. 10. A solid composite material according to claim 8 or 9, wherein the ratio of x to z (x / z) is in the range of 26 to 33.

11. 10. A solid composite material according to claim 8 or 9, wherein the ratio of x to z (x / z) is in the range of 28-30.

12. A solid composite material according to any one of claims 8 to 11, wherein x = 56.5 to 58.5 and y = 41.5 to 43.

5.

13. The solid composite material according to any one of claims 1 to 7, wherein the nanoparticles have an average particle size of 500 nm or less.

14. It has magnetic properties and is 70Am 2 / kg or more saturation magnetization M S and a coercive force Hc of 90 kA / m or more.

15. A solid composite material according to any one of claims 1 to 14, in the form of particles having a median particle size D50 of 500 µm or less, as determined by light scattering.

16. A solid composite material according to any one of claims 1 to 15, in which the content of τ-phase, excluding the dispersed nanoparticles made from material X, is equal to or greater than 80%.

17. A method for producing a solid composite material according to any one of claims 1 to 16, comprising the steps of: i. providing a composition comprising manganese, aluminum, and optionally carbon, and nanoparticles and / or one or more nanoparticle precursors in a molten state; ii. treating the composition obtained in step i so as to obtain solid particles comprising a MnAl alloy in the τ and / or ε phases; and iii. heat treating the particles obtained in step ii at a temperature of 350-700° C. for a period of 0.5-24 hours.

18. 18. The method of claim 17, wherein steps i, ii, and iii are performed in that order, and the temperature of the material does not exceed 700°C from the end of step i to the end of step iii.

19. 19. The method of claim 17 or 18, wherein step ii.a. comprises gas atomizing the material obtained from step i.

20. 20. The method of any one of claims 17 to 19, wherein step ii.b. comprises grinding the material at a temperature of -20°C or lower.

21. A method according to any one of claims 17 to 20, wherein step ii.b comprises grinding the material at a temperature of -150°C or lower.

22. The composition containing the composite material is then subjected to a process for preparing a composition having a size of at least 1×1×1 mm or a volume of at least 1 mm 3 forming the molded article into a molded article of A method for producing a molding comprising a solid composite material according to any one of claims 1 to 16 or obtainable by a method according to any one of claims 17 to 21.

23. 23. The method of claim 22, wherein the process of forming the molded object comprises one or more selected from extrusion, compression, additive manufacturing, and plastic molding.

24. A magnetic material in shaped form comprising a solid composite material according to any one of claims 1 to 16 or obtainable by the method according to any one of claims 17 to 21.

25. 25. An electric or electronic device comprising the magnetic material in shaped form according to claim 24.

Citation Information

Patent Citations

  • VC-added sintered rare-earth permanent magnet material and preparation method thereof

    CN108666064A

  • A permanent magnet alloy and a preparation method thereof

    CN109087766A

  • Anisotropic manganeseealuminummcarbon type alloy magnet

    JP1980031155A

  • Nanostructured Mn-Al Permanent Magnets And Methods of Producing Same

    US20120003114A1

  • Rare Earth-Free Permanent Magnetic Material

    US20180114614A1